Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

A memory-constrained multiscale pore network modeling framework for gas permeability prediction in compacted bentonite - Yongxiao Qu; Huaxiang Yan; Bo Li; LiGe Wang; Andrey P Jivkov; Weiguang Wang; Lin Ma; Mohsen Masihi; Qingrong Xiong (Computers and Geotechnics, 2026)

Effects of Lactobacillus- and Bacillus-based probiotics on growth performance, intestinal barrier function, and microbiota modulation in nursery pigs: A meta-analysis - K. Sahatsanon; A. Jayanegara; S.W. Kim; Y. Ruangpanit; C.-S. Lin; P. Sivapirunthep; C. Chaosap (Animal Feed Science and Technology, 2026)

Identification of extreme socioeconomic droughts considering heavy tailed distribution - Zonglin Zhou; Xinjun Tu; Yan Wang; Vijay P. Singh; Qingzhi Wen; Xiaohong Chen; Kairong Lin; Zhiyong Liu; Meixian Liu (Journal of Hydrology, 2026)

Particulate manganese shuttling shapes molybdenum and thallium isotope compositions in surface sediments of the Arabian Sea oxygen minimum zone - Xinming Chen; Niels A.G. M. van Helmond; Bing Xia; Hainan Lu; Zili Zhao; Yu Zhang; Lulu Wang; Yi-Bo Lin; Feifei Zhang; Gert-Jan Reichart; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2026)

The plastisphere: from microbial pollution to biodegradable solution - Wenfang Lin; Kai Yang; Tao Lu; Xiaoxi Kang; Xinyu Xing; Ewa Korzeniewska; Natalia P. Ivleva; Feng Ju; Haifeng Qian; Li Cui; Yong-guan Zhu (ENGINEERING Environment, 2026)
Microplastic pollution is threatening planetary health and sustainable development. The microbiota colonizing microplastic surfaces, termed the plastisphere, has emerged as artificial niches that harbor both microbial risks and novel biodegradation potential. However, these two aspects of the plastisphere have often been investigated in isolation. In this review, we first elaborate on how microplastics act as vectors in facilitating the enrichment and dissemination of pathogens, antibiotic resistance genes (ARGs), and even virus, thereby causing serious microbial and ecological risks, and eventually impacting human health. To address the potential risks, the key plastic-degrading resources, the underlying mechanisms, and recent advances in biodegradation technologies are synthesized. Given the dual roles of plastisphere microbes, we therefore propose a two-dimensional screening framework to identify safer and more efficient degraders. This review aims to guide the selection or synthesis of safe and highly efficient degrading microbial consortia, thereby providing sustainable and eco-friendly strategies for mitigating plastic pollution.

Associations of neighborhood racial and ethnic, economical, and educational segregation with breast cancer risk: The Multiethnic ohort Study - Ugonna Ihenacho; Jenna Khan-Gates; Katherine Lin; Janine V. Abe; Pushkar P. Inamdar; Juan Yang; Yuqing Li; Meera Sangaramoorthy; Christopher A. Haiman; Loïc Le Marchand; Lynne R. Wilkens; Scarlett Lin Gomez; et al. (Cancer Causes & Control, 2026)
Purpose Residential segregation is recognized as an upstream driver of poor health, yet few studies have evaluated its impact on breast cancer incidence at a local level. We examined associations of neighborhood residential segregation with breast cancer (BC) incidence in the Multiethnic Cohort Study (MEC). Methods Measures of Index of Concentration at the Extremes were developed to assess residential segregation by income, education, race and ethnicity, and racialized income. A prospective study (1993–1996 through December 2019) was conducted to examine associations of these measures and breast cancer incidence for 101,785 African American, Japanese American, Latina, Native Hawaiian, and White female participants in the MEC, aged 45–75 years at baseline and residing in California and Hawai‘i. Multivariable Cox regression was conducted to evaluate the associations of several residential segregation measures with breast cancer incidence (cases = 7,381) adjusting for demographic, lifestyle, and reproductive factors. Results In California, BC risk was higher for females residing in neighborhoods with the highest compared to lowest concentration of privilege by income segregation (quintile 5 [Q5] vs. Q1: hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.00–1.25, P trend = 0.001) and education segregation (Q5 vs. Q1: HR 1.15, 95% CI 1.01–1.31; P trend = 0.01). For Latina females, risks increased with increasing privilege for measures of income, education, race and ethnicity, and racialized income residential segregation ( P trends < 0.05). No associations were observed in Hawai‘i. Conclusion In California, residential economic privilege was independently associated with increased BC risk. Future studies should examine neighborhood- and individual-level pathways placing females residing in privileged areas at greater risk.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Magmatic evolution characteristics and heterogeneity of the outer zone of the Emeishan Large Igneous Province: a case study of basalts from the Tianquan and Huayingshan areas - C. C. Li; S. Yang; Z. Y. Lin; Y. P. Jing; Y. Xia; Y. H. Chen; J. T. Liao; C. D. Nie (Australian Journal of Earth Sciences, 2026)

Tropical legume plants benefit more when grown with interspecific plants than intraspecific under soil phosphorus-limited conditions - Jan Sher; Yun-Bing Zhang; Ghulam Mujtaba Shah; Stephen P. Bonser; Jiao-Lin Zhang (Plant and Soil, 2026)

Retraction notice to “Boron contamination and its risk management in terrestrial and aquatic environmental settings” [Sci. Total Environ. 894 (2023) 164744] - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2026)

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

A Musculoskeletal-Finite Element Study of Knee Joint Loading and Cartilage Mechanics in Children with Cerebral Palsy - Dongfei Huo; Run Lin; Junyan Li; Timothy P. Holsgrove; Dominic Farris; Dong Wang; Xijin Hua (Annals of Biomedical Engineering, 2026)
Purpose Cerebral palsy (CP) is typically associated with abnormal gait that may alter knee joint loading and accelerate joint degeneration. We developed an integrated musculoskeletal-finite element (MSK-FE) framework to quantify differences in knee joint biomechanics between children with CP and typically developing (TD) peers. Methods Gait data from 13 children (TD, n = 5; hemiplegia [HP], n = 4; diplegia [DP], n = 4) were analyzed using OpenSim to obtain knee kinematics and compressive knee joint reaction forces (KJRFs). These were applied to scaled 3D FE knee models, incorporating biphasic cartilage, menisci, and ligaments, at the first force peak, mid-stance, and second force peak to evaluate cartilage pressures. Results Compared with TD, both CP subtypes (HP and DP) exhibited greater knee flexion throughout the gait cycle, except for the affected limb in HP (HP A ), which showed reduced flexion during the stance phase. Peak KJRFs over the gait cycle were slightly higher in DP and HP A than in TD, whereas the unaffected limb in HP (HP UA ) generated the highest peak KJRFs among all groups, indicating compensatory overloading of the unaffected limb in HP. Correspondingly, FE analysis showed that peak cartilage contact pressures in the HP cohorts were significantly higher than in DP and TD, while pressures in DP were slightly higher than in TD over the gait cycle. The HP UA showed the highest contact pressures among all groups. Conclusion The MSK-FE framework quantified knee loading and cartilage contact pressure patterns in children with CP. These preliminary findings highlight subtype- and limb-specific gait-loading patterns and provide a mechanistic basis for future larger-scale and longitudinal investigations.

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part Two: non-parasitic conditions - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Levels and emission factors of polycyclic aromatic hydrocarbons in night market cooking fumes - Thi-Hieu Le; Cindy Soo Yun Tan; Hsin-Chieh Kung; Riza P. Gumaling; Danielle E. Que; How-Ran Chao; Ying I. Tsai; Xuan-Thanh Bui; Guo-Ping Chang-Chien; Lin-Chi Wang (Atmospheric Environment, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Mind the Gap: Human and AI Uncertainties in Cardiac MRI Segmentation - Qiao Lin; Xin Chen; Chao Chen; Nikesh Jathanna; Peter P. Swoboda; Shahnaz Jamil-Copley; Jonathan M. Garibaldi (Cardiovascular Engineering and Technology, 2026)

Subject-specific whole-lung CFPD coupled with PBPK/PD to predict inhaled bronchodilator response in asthmatic and healthy subjects - Prathish K. Rajaraman; Xuan Zhang; Alejandro P. Comellas; Eric A. Hoffman; Ching-Long Lin (Journal of Aerosol Science, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Susceptibility to eight common chemical insecticides in Helicoverpa zea populations from the southern United States - Bhavana Patla; Tiago Silva; Shucong Lin; Graham P. Head; Francis P.F. Reay-Jones; Xinzhi Ni; Lina Bernaola; Sebe Brown; Don Cook; James Villegas; Jeffrey A. Davis; Fangneng Huang (Crop Protection, 2026)

Flocculation dynamics of suspended particulate matter under various tidal conditions - Mingze Lin; Xiaoteng Shen; Changjian Xu; Michael Fettweis; Byung Joon Lee; Qilong Bi; Peter Robins; Xiaorong Li; Jerome P.-Y. Maa; Gang Wang (Journal of Hydrology, 2026)

Selective degradation of tetracyclines in the Mn(II)/H2O2/HCO3 process with low peroxide dosage: The neglected role of complexation-mediated electron transfer - Yimin Lin; Ruike Men; Yinhao Dai; Ivan P. Pozdnyakov; Hongyu Dong; Xiaohong Guan (Journal of Hazardous Materials, 2026)

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part One: parasites - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

A New Shear Strength Model for Filled Discontinuities Based on the Disturbed State Concept Theory - Hang Lin; Hailong Bie; Zhanming Shi; Jiangteng Li; P. G. Ranjith; Yujun Zuo (Rock Mechanics and Rock Engineering, 2026)

Corrigendum to “Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum” [Geochim. Cosmochim. Acta 411 (2025) 233–249] - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2026)

Ecological responses of the largest lake-wetland system (North China Plain) to hydrological regulation and cultural eutrophication over the past 70 years - Longjuan Cheng; John P. Smol; Qi Lin; Chaoran Wei; Shuyi Yang; Dejun Wan; Qingfeng Jiang; Dongliang Ning; Bin Xue (Anthropocene, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to extreme heat and autism in children - David G. Luglio; Xin Yu; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Nathan Pavlovic; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Assessment of dynamic drought risk and transition characteristics by combining an indicator-based approach and Markov chain model - Bin Huang; Tao Peng; Tianyi Fan; Vijay P. Singh; Xiaohua Dong; Qingxia Lin; Wenjuan Chang; Ji Liu; Yan Huang; Jiali Guo; Yinghai Li; Dan Yu (Natural Hazards, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Individual‐Level Trait Responses in Cyanobacterial Populations and Communities - Arnaud P. Louchart; Annemieke M. Drost; Chaohong Lin; Suzanne M. H. Naus‐Wiezer; Zhipeng Duan; Elena Litchman; Dedmer B. Van de Waal (Ecology Letters, 2026)
Trait‐based approaches support the mechanistic understanding of individual organism responses to resource availabilities that underlie population and community dynamics. For microbes such as phytoplankton, however, it remains challenging to obtain individual cell traits, particularly in natural communities. Here, we provide a flow cytometry‐based approach using a freshwater cyanobacterium Microcystis spp. culture and assessed individual‐level trait responses to nitrogen, phosphorus and light limitation and high p CO 2 . Then, these responses served as ‘fingerprints’ to describe the main drivers in natural cyanobacterial communities. We observed distinct responses in multidimensional trait space, that is, the integrated phenotype, which differed particularly between nitrogen and light limitation. Notably, cellular contents of the pigments phycocyanin and chlorophyll‐a decreased with nitrogen limitation and increased with light limitation, which was confirmed in natural communities. Overall, our results show how individual‐trait responses to known environmental conditions can be used to understand natural cyanobacterial population and community dynamics.

A new mineral quantification method via global feature fusion of plane-polarized and cross-polarized light images: MQM-p/xpl - W. Ma; Z.H. Xu; P. Lin; S. Li (Minerals Engineering, 2026)

Coupled surface water-groundwater-crop model considering the impact of irrigation using different calibration targets - Yuliang Zhang; Jiejie Zhang; Vijay P. Singh; Yuliang Zhou; Yi Cui; Qingxia Lin; Juliang Jin; Shaowei Ning; Zhiyong Wu; Rongxing Zhou; Jieru Yan; Shiqin Xu (Journal of Hydrology, 2026)

A least-squares spatio-temporal adjustment algorithm (LSSTAA) for radiometric normalization of PlanetScope time series - Lin Yan; David P. Roy; Haiyan Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A control engineering perspective on the advantages of efference copies - Benjamin P. Campbell; Huai-Ti Lin; Holger G. Krapp (Biological Cybernetics, 2025)
Biological systems have evolved to perform high-speed voluntary movements whilst maintaining robustness and stability. This paper examines a control architecture based on the principles of efference copies found in insect sensorimotor control which we call the fully-separable-degrees-of-freedom (FSDoF) controller. Within a control engineering framework, we benchmark the advantages of this control architecture against two common engineering control schemes: a pure feedback (PFB) controller and a Smith predictor (SP). Our study identifies three advantages of the FSDoF for biology. It is advantageous in controlling systems with sensor delays, and it can effectively handle noise. Thirdly, it allows biological sensors to increase their operating range. We evaluate the robustness of the FSDoF controller and show that it achieves improved performance with equal stability margins and robustness. Finally, we discuss variations of the FSDoF which theoretically provide the same performance.

Associations between concurrent neonicotinoid, pyrethroid, and organophosphate insecticide metabolites and neurocognitive performance in Ecuadorian adolescents - Jessica Yen; Kun Yang; Tuo Lin; Xin M. Tu; Georgia Kayser; Rajendra P. Parajuli; Ana Skomal; Sheila Gahagan; Jose Suarez-Torres; Suzi Hong; Raeanne C. Moore; Jose R. Suarez-Lopez (Science of The Total Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Association between prenatal exposures to per- and polyfluoroalkyl substances and early language development in the ECHO cohort - Patricia Cintora; Lesliam Quirós-Alcalá; Adaeze W. Nzegwu; Sudhi Upadhyaya; Megan Woodbury; Sarah Dee Geiger; Rachel Morello-Frosch; Anne L. Dunlop; Theresa M. Bastain; Anne P. Starling; Dana Dabelea; Carlos A. Camargo; et al. (NeuroToxicology, 2025)

Generation of carbon dioxide anion radical by UV/small molecular monocarboxylic acid system for reductive dechlorination of chlorinated alkanes - Li-Zhi Huang; Jingjing Lin; Weiguo Chen; Wei Wang; Yitao Dai; Ivan P. Pozdnyakov; Bingbing Hu (Journal of Environmental Sciences, 2025)

Soil iGDGTs temperature dependence: From the Tibetan Plateau to the global scale and its implications for the Holocene temperature conundrum - Yanwu Duan; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Yuling Zhou; Yuanxin Li; Mengjing Li; Lin Chen; Xianyong Cao; Fahu Chen (Geochimica et Cosmochimica Acta, 2025)

Divergent environmental controls on branched tetraethers along precipitation gradients in soils of the Tibetan Plateau - Yanwu Duan; Yuling Zhou; Shuo Hao; Qing Sun; Josef P. Werne; Aifeng Zhou; Lin Chen; Yuanxin Li; Mengjing Li; Xianyong Cao; Fahu Chen (Chemical Geology, 2025)

A Genomic Exploration of the Possible De‐Extirpation of the Zanzibar Leopard - Xin Sun; Emily Louisa Cavill; Ashot Margaryan; Jianqing Lin; Søren Thingaard; Tamrini A. Said; Shyam Gopalakrishnan; M. Thomas P. Gilbert (Molecular Ecology, 2025)
The recently extirpated Zanzibar leopard was the only known African leopard ( Panthera pardus spp.) population restricted exclusively to a major island habitat. Although its demise was driven through habitat change and conflict with humans, given its role as a keystone species for the Zanzibar Archipelago, its successful potential reintroduction might offer a means for helping preserve the natural biodiversity of its former habitat. Whether this is feasible, however, would be contingent on both whether closely related source populations can be identified on mainland Africa, and whether the Zanzibar form exhibited any special adaptations that might need to be considered when choosing such a source. In light of these questions, we genomically profiled two of the six known historic specimens, to explore whether they represent a realistic candidate for de‐extirpation through reintroduction. Our analyses indicate that despite its geographical separation, the Zanzibar leopard shared a close genetic relationship with mainland East African individuals. Furthermore, although its uniqueness as an island population was emphasised by genomic signatures of high inbreeding and increased mutation load, the latter similar to the level of the critically endangered Amur leopard ( P. p. orientalis ), we find no evidence of functionally significant genetic diversity unique to Zanzibar. We therefore conclude that should attempts to restore leopards to Zanzibar be considered, then mainland East African leopards would provide a suitable gene pool.

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Fetal response to maternal exposures of environmental chemicals: Utility of a four-cell human feto-maternal interface organ-on-chip - Haley L. Moyer; SungJin Kim; Bowie P. Lam; Lauren S. Richardson; Han-Hsuan D. Tsai; Lucie C. Ford; Hsing-Chieh C. Lin; Weihsueh A. Chiu; Ramkumar Menon; Arum Han; Ivan Rusyn (Chemico-Biological Interactions, 2025)

Electron diffraction-guided natural product discovery: identification and isolation of new scaffold class from Podospora australis - David A. Delgadillo; Lin Wu; Jessica E. Burch; Lygia Silva de Moraes; Caroline Wang; Benjamin P. Tu; Yi Tang; Hosea M. Nelson (Phytochemistry Letters, 2025)

Mediating Pathways Between Food Insecurity and Later-age Sleep Quality - J. Wang; J. Luo; H. Lin; P. Quinn; A. Chow (Journal of the Academy of Nutrition and Dietetics, 2025)

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

Histopathological and immunohistochemical characterisation of inflammatory lesions in flying foxes naturally infected with Australian Bat Lyssavirus (ABLV). - Y. Lin Tan; M. Gimeno; P. Pinczowski; S. Gestier; E. Hall; M. Krockenberger (Journal of Comparative Pathology, 2025)

An innovative adaptive mineral segmentation method via augmentation and fusion of single and orthogonal polarized images: AMS-p/xpl - W. Ma; P. Lin; S. Li; Z.H. Xu (Computers & Geosciences, 2025)

Sustainable relay strategy for the synthesis of d-glucose-based poly ionic liquid and its fabrication on carbon electrode for simultaneous detection of chromium (VI) and lead (II) in environmental waters - Krishnaraj P; Lokesh Kumar Sugumar; Bhulakshmi Sathi; Chun-Cheng Lin; Sheng-kai Wang; Kishore K.R. Tetala; Sabbasani Rajasekhara Reddy (Chemical Engineering Journal, 2025)

Impaired early type I interferon responses to influenza virus infection in aged mice are associated with subsequent increased pulmonary inflammation - Wenxin Wu; Jeremy S. Alexander; J. Leland Booth; Chaoqun Huang; Lin Liu; Craig A. Miller; Douglas A. Drevets; Jordan P. Metcalf (GeroScience, 2025)

Navigating disclosure in new romantic partnerships as an adolescent or young adult with Li-Fraumeni syndrome - Camella J. Rising; Chloe O. Huelsnitz; Rowan Forbes Shepherd; Catherine Wilsnack; Patrick Boyd; Alix G. Sleight; Ashley S. Thompson; Sadie P. Hutson; Payal P. Khincha; Allison Werner-Lin (Familial Cancer, 2025)
Li-Fraumeni syndrome (LFS) is an early-onset cancer syndrome caused by pathogenic germline TP53 variants. Adolescents and young adults (AYAs) with LFS may have challenges navigating new romantic partnerships given the significant effects of LFS on multiple life domains that also affect partners (e.g., reproductive decision-making). Disclosing LFS-related information to new partners may be especially difficult given the uncertainty, complexity, and chronicity of LFS. This qualitative-descriptive study aimed to explore AYAs’ LFS disclosure decisions and experiences in new romantic partnerships. Participants were individuals with LFS aged 15–39 years at enrollment in a National Cancer Institute study. The analytic sample included 33 AYAs who completed at least one telephone interview. Greene’s disclosure decision-making model guided thematic analysis. Participants were mostly female (67%) and married/in a long-term relationship (58%), with mean age 29 years and ≥ 1 primary cancer (61%). Key factors in LFS disclosure decision-making included perceived relevancy to partners (e.g., future children’s genetic risk), partner traits (e.g., trustworthiness), and relationship quality (e.g., closeness). AYAs described LFS disclosures in new partnerships as a process. Disclosing LFS diagnosis often occurred early to fulfill a sense of moral obligation and emotionally self-protect from future rejection, while subsequent LFS disclosures depended on relationship quality and the topic’s emotional valence or complexity. Partners often earned AYAs’ trust by demonstrating a willingness to learn about and try to understand LFS. Clinicians and LFS communities could support AYAs by providing opportunities to discuss, normalize, and ameliorate challenges with LFS disclosures in new romantic partnerships (e.g., peer support groups, psychotherapy).

P20-17 Polyethylene terephthalate (PET) nanoplastics induce acute pulmonary inflammation in mice - Ø.P. Haugen; L.M.A. Camassa; H.F. Berntsen; F.-C. Lin; V. Alcolea-Rodriguez; R. Portela; F. Barbero; O.A.H. Foss; H. Sadeghiankaffash; Ø. Skare; S. Alsaedi; A.L. Moen; et al. (Toxicology Letters, 2025)

Museomics and Salvaged Feathers Piece Together the Evolutionary History and Conservation Genomics of the Elusive, Critically Endangered Night Parrot ( Pezoporus occidentalis ) - Heng Lin Yeap; Gunjan Pandey; Jeremy J. Austin; John G. Oakeshott; Christopher M. Hardy; Stephen A. Murphy; Nicholas P. Leseberg; Allan H. Burbidge; Kenny J. Travouillon; Leo Joseph; Anna M. Kearns (Molecular Ecology, 2025)
The Night Parrot is a critically endangered nocturnal bird of Australia's arid zone. The species was “lost” for most of the 20th century until its rediscovery in 1990. Extant populations are now known in eastern and western Australia, but the species has been extirpated from much of its historical range. Here we estimate critically needed Essential Biodiversity Variables (EBVs) for the Night Parrot from historical and opportunistically collected contemporary samples. We find little population structure across the species' range and evidence of recent connectivity between extant populations ~2000 km apart. Most eastern individuals show significant kinship with one another, as did two from an extinct population in southern Australia. Heterozygosity is similarly low in all extant populations but ten‐fold lower in the extinct population sampled. Coalescent modelling of effective population size ( Ne ) suggests that Night Parrot numbers were reasonably high until around 90 years ago when Ne crashed from ~10,000 to ~100. Current Ne is now at its lowest in the past several million years. Our findings will help guide the ongoing management of one of Australia's most threatened birds.

Metrics of Urbanicity and Rurality in US-Based Epidemiologic Studies of Ambient Temperature and Health: A Scoping Review - Nicholaus P. Johnson; Alexandra Del Favero-Campbell; Amruta Nori-Sarma; Audrey Amezcua-Smith; Brandon Lewis; Chen Chen; Chengyi Lin; Damien Foo; Garam Byun; Hayon Michelle Choi; Honghyok Kim; Jesse D. Berman; et al. (Current Environmental Health Reports, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Built environment, car ownership and PM2.5: Stronger causal estimates from a quasi-experiment - Lin Shi; Yiliang Jiang; Faan Chen; Kaiyi Zhu; Chris P. Nielsen; Yuejiao Wang; Fang Tian; Jiaorong Wu; Xiaohong Chen (Journal of Transport Geography, 2025)

Industrial air pollution and newborn hearing screening failure - Yanhong Huang; Yan Lin; Roberta P. Lavin; Li Luo; Ming Luo; Shuguang Leng; Netanya M. Mullen; Karen Hawley; Xi Gong (Journal of Hazardous Materials, 2025)

A decade-long meta-analysis of risks posed by pesticides in Chinese surface waters - Jiuying Li; Lin Hou; Na Liu; Kaifeng Rao; Jing Zheng; Jian Xu; John P. Giesy; Xiaowei Jin (Journal of Environmental Management, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Shifts in soil prokaryotic community structure due to clear-cutting secondary Acacia mangium forests and replacing with Eucalyptus urophylla - Yun-Long Zhang; Ning Pan; Wen-Tao Qiao; Richard P. Dick; Dao-Lin Du; Kun Chen; Shan-Shan Qi; Yan Li; Yi Zhou; Yong-Feng Wang (Journal of Environmental Management, 2025)

Discordant sibling analysis of autism risk associated with prenatal exposure to tailpipe and non-tailpipe particulate matter pollution - Anny H. Xiang; Jane C. Lin; Ting Chow; Xin Yu; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Michael J. Kleeman; Rob McConnell; Md. Mostafijur Rahman (Environmental Research, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Penetration of groundwater into crystalline rocks - Bruce W. D. Yardley; Roy A. Wogelius; Thomas Mueller; Antoni E. Milodowski; Lorraine P. Field; Lin Ma; Richard Metcalfe; Simon Norris (Hydrogeology Journal, 2025)

Genomic and metabolic characterisation of a novel species Magnetominusculus dajiuhuensis DJH-1Ts sp. nov. from an acidic peatland - Pranami Goswami; Runjia Ji; Jianxun Shen; Andrew P. Roberts; Wei Lin (Systematic and Applied Microbiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Dynamic response of vegetation to meteorological drought and driving mechanisms in Mongolian Plateau - Shenghang Gao; Shengzhi Huang; Vijay P. Singh; Xiaoya Deng; Limin Duan; Guoyong Leng; Wenwen Guo; Yifei Li; Lin Zhang; Zhiming Han; Qiang Huang (Journal of Hydrology, 2025)

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

Synthesis and Biological Evaluation of Novel Triazine Analogs as Rad6 Inhibitors - Qian Lin; Ambikai Gajan; Ignatius Nguyen; Shiv Sharma; Pratima Nangia-Makker; Steven Firestine; Malathy P. Shekhar (Pharmaceutical Research, 2025)

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Inheritance of Cry2Ab2 resistance in two Helicoverpa zea (Lepidoptera: Noctuidae) populations resistant to single- and dual-Bacillus thuringiensis proteins - Fangneng Huang; Wenbo Yu; Graham P. Head; Ying Niu; Caroline Sakuno; Shucong Lin; Tiago Silva; Bhavana Patla (Journal of Invertebrate Pathology, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Spatial and temporal variation in benthic foraminiferal assemblages record history of human activities within the Matagorda Bay system - Paige P. Klug; Christina L. Belanger; Timothy Dellapenna; Yoonho Jung; Anna M. Mozisek; Zachary Clore; Peng Lin; Wei Xing; Danielle Fehrenbach; J.T. Bowling; Gael Ndi Nkwain (Estuarine, Coastal and Shelf Science, 2025)

Integrated models of nutrient dynamics in lake and reservoir watersheds: A systematic review and integrated modelling decision pathway - Floran Clopin; Ilaria Micella; Jorrit P. Mesman; Ma Cristina Paule-Mercado; Marina Amadori; Shuqi Lin; Lisette N. de Senerpont Domis; Jeroen J.M. de Klein (Environmental Modelling & Software, 2025)

pH-tolerant high internal phase Pickering emulsions stabilized by photo-responsive host–guest supramolecular polymers - Feilin Lin; Siyu Wang; Bernard P. Binks; Jianzhong Jiang (Chemical Engineering Journal, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Toward reproducible and interoperable environmental modeling: Integration of HydroShare with server-side methods for exposing large-extent spatial datasets to models - Young-Don Choi; Iman Maghami; Jonathan L. Goodall; Lawrence Band; Ayman Nassar; Laurence Lin; Linnea Saby; Zhiyu Li; Shaowen Wang; Chris Calloway; Hong Yi; Martin Seul; et al. (Environmental Modelling & Software, 2025)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Investigation of inter-subject variation in ultrafine particle deposition across human nasal airways: A study involving children, adults, and the elderly - Qinyuan Sun; Ya Zhang; Lin Tian; Jiyuan Tu; Richard Corley; Andrew P. Kuprat; Jingliang Dong (Science of The Total Environment, 2024)

Decomposing the variance: The unique and shared associations of fine and ultrafine particulate matter exposed during pregnancy with child autism spectrum disorder - Xin Yu; Michael J. Kleeman; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Jiu-Chiuan Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2024)

Land-atmosphere and ocean–atmosphere couplings dominate the dynamics of agricultural drought predictability in the Loess Plateau, China - Jing Luo; Shengzhi Huang; Yu Wang; Vijay P. Singh; Junguo Liu; Qiang Huang; Guoyong Leng; Ji Li; Haijiang Wu; Xudong Zheng; Wenwen Guo; Xue Lin; et al. (Journal of Hydrology, 2024)

Corrigendum to Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva [Environ. Res. 216P4 (2023) 114846] - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Enhanced global dust counteracted greenhouse warming during the mid- to late-Holocene - Shiwei Jiang; Xin Zhou; Jasper F. Kok; Qifan Lin; Yonggang Liu; Tao Zhan; Yanan Shen; Zhibo Li; Xuanqiao Liu; Anze Chen; Luo Wang; Wen Chen; et al. (Earth-Science Reviews, 2024)

The effect of cross-regional transport on ozone and particulate matter pollution in China: A review of methodology and current knowledge - Kun Qu; Yu Yan; Xuesong Wang; Xipeng Jin; Mihalis Vrekoussis; Maria Kanakidou; Guy P. Brasseur; Tingkun Lin; Teng Xiao; Xuhui Cai; Limin Zeng; Yuanhang Zhang (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Identification of pollution sources in rivers by downstream analysis of low-concentration elements associated with wastewater - H.-C. Lin; P.-Y. Hsieh; G.-S. Wang; D.-W. Wang; T.-H. Wang; Y.-C. Hsu; C.-F. Wu (International Journal of Environmental Science and Technology, 2024)

Nonlinear contributions of surface solar brightening to maize yield gains in the US Corn Belt - H. Zhao; H. Yang; T.J. Avenson; G.F. Sassenrath; MB. Kirkham; S.W. Welch; L. Zhang; N. Wan; A.M. Nelson; P. Gowda; X. Lin (Agricultural and Forest Meteorology, 2024)

Quantifying the Role of the Eddy Transfer Coefficient in Simulating the Response of the Southern Ocean Meridional Overturning Circulation to Enhanced Westerlies in a Coarse-resolution Model - Yiwen Li; Hailong Liu; Pengfei Lin; Eric P. Chassignet; Zipeng Yu; Fanghua Wu (Advances in Atmospheric Sciences, 2024)

An in vitro-in silico workflow for predicting renal clearance of PFAS - Hsing-Chieh Lin; Courtney Sakolish; Haley L. Moyer; Paul L. Carmichael; Maria T. Baltazar; Stephen S. Ferguson; Jason P. Stanko; Philip Hewitt; Ivan Rusyn; Weihsueh A. Chiu (Toxicology and Applied Pharmacology, 2024)

Samarium-doped vanadium pentoxide nanorods anchored reduced graphene oxide nanocomposite as a bi-functional electrode material for supercapacitor and direct methanol oxidation fuel cell applications - V. Uma Shankar; Yuttana Mona; P. Suganya; P. Senthil Kumar; D. Govindarajan; V. Mangla Gowri; E. Narayanamoorthi; Pei-Chien Tsai; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Process Safety and Environmental Protection, 2024)

Spatial variation in genomic signatures of local adaptation during the cane toad invasion of Australia - Marc A. Beer; Daryl R. Trumbo; Rhett M. Rautsaw; Christopher P. Kozakiewicz; Brendan Epstein; Paul A. Hohenlohe; Ross A. Alford; Lin Schwarzkopf; Andrew Storfer (Molecular Ecology, 2024)
Adaptive evolution can facilitate species' range expansions across environmentally heterogeneous landscapes. However, serial founder effects can limit the efficacy of selection, and the evolution of increased dispersal during range expansions may result in gene flow swamping local adaptation. Here, we study how genetic drift, gene flow and selection interact during the cane toad's ( Rhinella marina ) invasion across the heterogeneous landscape of Australia. Following its introduction in 1935, the cane toad colonised eastern Australia and established several stable range edges. The ongoing, more rapid range expansion in north‐central Australia has occurred concomitant with an evolved increase in dispersal capacity. Using reduced representation genomic data of Australian cane toads from the expansion front and from two areas of their established range, we test the hypothesis that high gene flow constrains local adaptation at the expansion front relative to established areas. Genetic analyses indicate the three study areas are genetically distinct but show similar levels of allelic richness, heterozygosity and inbreeding. Markedly higher gene flow or recency of colonisation at the expansion front have likely hindered local adaptation at the time of sampling, as indicated by reduced slopes of genetic‐environment associations (GEAs) estimated using a novel application of geographically weighted regression that accounts for allele surfing; GEA slopes are significantly steeper in established parts of the range. Our work bolsters evidence supporting adaptation of invasive species post‐introduction and adds novel evidence for differing strengths of evolutionary forces among geographic areas with different invasion histories.

Sedimentary biogeochemical gradients across the Sunda Shelf in the South China Sea and correlations with satellite observations - Yuanfang Zhang; Lin Deng; Zaiming Ge; Lin Guo; Qian P. Li (Frontiers in Marine Science, 2024)
The sediment biogeochemistry of phosphorus (P) and biogenic silica (BSi) in the southern South China Sea shelf (SSCS) is inadequate understood. Here, we examine the spatial distributions of P species and BSi in surface sediments across the Sunda Shelf and explore their relationships with satellite data of sea surface chlorophyll-a (Chla), suspended particulate matter (SPM), particulate organic carbon, particulate inorganic carbon, primary production (PP), and phytoplankton functional types. The total sediment P (TSP), in the range from 283.94 to 579.94 μg/g dry sediment, was dominated by inorganic P with higher levels in stations outside the Lupar and Saribas estuaries. The TSP was composed of seven different P species including Ca-IP and Ca-OP (58%), Detr-P (15%), Exch-P (11%), Fe-IP (10%), Ref-P (4%) and Ads-IP (2%) based on a sequential extraction method. The concentrations of various sediment P species were found significantly correlated with satellite climatological SPM, diatom biomass, and monthly climatological pico-PP revealing the importance of biological production for the sediment P storage, whereas the sediment BSi concentration showed no correlations with any of the above satellite products. An elevated R 2 value in the regression of BSi with the in-situ depth-integrated Chla points to the need of developing satellite algorithms with vertical profiles from space. Finally, we argue that future studies of the SSCS sediment biogeochemistry may be benefited from data of hyperspectral and geostationary satellites.

Associations of a toenail metal mixture with attention and memory in the Gulf long-term follow-up (GuLF) study - Joyce J.Y. Lin; Jordan R. Kuiper; Aisha S. Dickerson; Jessie P. Buckley; Heather E. Volk; Diane S. Rohlman; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Lawrence S. Engel; Ana M. Rule (Science of The Total Environment, 2024)

Reconstruction of seamless harmonized Landsat Sentinel-2 (HLS) time series via self-supervised learning - Hao Liu; Hankui K. Zhang; Bo Huang; Lin Yan; Khuong K. Tran; Yuean Qiu; Xiaoyang Zhang; David P. Roy (Remote Sensing of Environment, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Dislocation-mediated interfacial re-equilibration of pyrite: An alternative model to interface-coupled dissolution-reprecipitation and gold remobilisation - Denis Fougerouse; Steven M. Reddy; Sumail; Joël Brugger; Nicolas Thébaud; William D.A. Rickard; Lin Yang; Zakaria Quadir; Malcolm P. Roberts; Andrew G. Tomkins; Laure Martin; Laura Petrella; et al. (Geochimica et Cosmochimica Acta, 2024)

Marine macro-litter sources and ecological impact: a review - Van-Giang Le; Hoang-Lam Nguyen; Minh-Ky Nguyen; Chitsan Lin; Nguyen T. Quang Hung; Akhil P. Khedulkar; Nguyen K. Hue; Phung T. Thu Trang; Arvind Kumar Mungray; D. Duc Nguyen (Environmental Chemistry Letters, 2024)

Change in rate of healthcare encounters for respiratory infection from air pollution exposure after improved vehicle emissions standards in New York State - Daniel P. Croft; Mark J. Utell; Han Liu; Shao Lin; Philip K. Hopke; Sally W. Thurston; Yunle Chen; David Q. Rich (Air Quality, Atmosphere & Health, 2024)
The introduction of Tier 3 light-duty vehicles with reduced emissions began in New York State (NYS) in 2017, with required compliance by 2025. We hypothesized that improved air quality during the early implementation of Tier 3 (2017–2019) would result in reduced rates of hospitalizations and emergency department (ED) visits for respiratory infection associated with increased PM 2.5 compared to 2014–2016 (pre-Tier 3). Using data on adult patients hospitalized or having an ED visit for influenza, upper respiratory infection, culture-negative pneumonia, or respiratory bacterial infection, living within 15 miles of six air quality monitoring sites in NY, and a case-crossover design and conditional logistic regression, we estimated the rates of respiratory infection hospitalizations and ED visits associated with increased ambient PM 2.5 concentrations in the previous 0–6 days and each week thereafter up to 1 month. Interquartile range (IQR) increases in PM 2.5 in the previous 6 days were associated with 4.6% (95% CI: − 0.5, 10.1) and 11.9% (95% CI = 6.1, 18.0) increased rates of influenza hospitalizations in 2014–2016 and 2017–2019, respectively. This pattern of larger relative rates in 2017–2019 observed at all lag times was only present in males hospitalized for influenza but not other infections or in females. The rates of respiratory infection visits associated with increased PM 2.5 were generally not reduced in this early Tier 3 implementation period compared to 2014–2016. Limited fleet penetration of Tier 3 vehicles and differences in particle deposition, infection type, and sex by period may all have contributed to this lack of improvement.

Determinants of microbiome composition: Insights from free‐ranging hybrid zebras ( Equus quagga × grevyi ) - Joel O. Abraham; Bing Lin; Audrey E. Miller; Lucas P. Henry; Margaret Y. Demmel; Rosemary Warungu; Margaret Mwangi; Patrick M. Lobura; Luisa F. Pallares; Julien F. Ayroles; Robert M. Pringle; Daniel I. Rubenstein (Molecular Ecology, 2024)
The composition of mammalian gut microbiomes is highly conserved within species, yet the mechanisms by which microbiome composition is transmitted and maintained within lineages of wild animals remain unclear. Mutually compatible hypotheses exist, including that microbiome fidelity results from inherited dietary habits, shared environmental exposure, morphophysiological filtering and/or maternal effects. Interspecific hybrids are a promising system in which to interrogate the determinants of microbiome composition because hybrids can decouple traits and processes that are otherwise co‐inherited in their parent species. We used a population of free‐living hybrid zebras ( Equus quagga × grevyi ) in Kenya to evaluate the roles of these four mechanisms in regulating microbiome composition. We analysed faecal DNA for both the trn L‐P6 and the 16S rRNA V4 region to characterize the diets and microbiomes of the hybrid zebra and of their parent species, plains zebra ( E. quagga ) and Grevy's zebra ( E. grevyi ). We found that both diet and microbiome composition clustered by species, and that hybrid diets and microbiomes were largely nested within those of the maternal species, plains zebra. Hybrid microbiomes were less variable than those of either parent species where they co‐occurred. Diet and microbiome composition were strongly correlated, although the strength of this correlation varied between species. These patterns are most consistent with the maternal‐effects hypothesis, somewhat consistent with the diet hypothesis, and largely inconsistent with the environmental‐sourcing and morphophysiological‐filtering hypotheses. Maternal transmittance likely operates in conjunction with inherited feeding habits to conserve microbiome composition within species.

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Global response of different types of grasslands to precipitation and grazing, especially belowground biomass - Xi Lin; Hongbin Zhao; Shengwei Zhang; Vijay P. Singh; Ruishen Li; Meng Luo; Shuai Wang; Xingyu Zhao; Shengwei Lv; Xinghui Chen (Agriculture, Ecosystems & Environment, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Characterization of type II IFNs and their receptors in a cyprinid fish, the blunt snout bream Megalobrama amblycephala - Bo Li; Shan Nan Chen; Lin Huang; Li Li; Li Ren; Jing Hou; Jing Yun Tian; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

Treatment of Lateral Canthal Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-2 Phase 3 Trial - Glynis Ablon; David Bank; Theda Kontis; Sherrif F Ibrahim; Melanie Palm; Sue Ellen Cox; Jason K Rivers; Lisa Grunebaum; Mitchel P Goldman; Shannon Humphrey; Xiaoming Lin; Schafiq Nabhani; et al. (Toxicon, 2024)

Vegetation-cover control of between-site soil temperature evolution in a sandy desertland - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Yalu Han; Shuang Feng; Lin Miao; Chen Liu (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Estimation of probability of capsizing with split-time method - Vadim Belenky; Kenneth M. Weems; Woei-Min Lin; Vladas Pipiras; Themistoklis P. Sapsis (Ocean Engineering, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Route-to-market strategy for low-carbon hydrogen from natural gas in the Permian Basin - Ning Lin; Yayun Chen; Maria P Madariaga (Fuel, 2024)

Downregulation of the expression of subgenomic chromosome A7 genes promotes plant height in resynthesized allopolyploid Brassica napus - Kanglu Zhao; Jing Dong; Junxiong Xu; Yanbo Bai; Yuhe Yin; Chunshen Long; Lei Wu; Tuanrong Lin; Longqiu Fan; Yufeng Wang; Patrick P. Edger; Zhiyong Xiong (Theoretical and Applied Genetics, 2024)

A framework for water supply regulation in coastal areas by avoiding saltwater withdrawal considering upstream streamflow distribution - Haiou Wu; Xinjun Tu; Xiaohong Chen; Vijay P. Singh; Leonardo Alfonso; Kairong Lin; Zhiyong Liu; Rongbiao Lai (Science of The Total Environment, 2023)

Role of diatom-derived oxylipins in organic phosphorus recycling during coastal diatom blooms in the northern South China Sea - Zhengchao Wu; Qian P. Li; Richard B. Rivkin; Senjie Lin (Science of The Total Environment, 2023)

Drought prediction: Insights from the fusion of LSTM and multi-source factors - Tian Wang; Xinjun Tu; Vijay P. Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou (Science of The Total Environment, 2023)

Fragmentation of continental subduction is ending the Himalayan orogeny - Xiaofeng Liang; Yang Chu; Bo Wan; Ling Chen; Lin Chen; Eric Sandvol; Stephen P. Grand; Yibing Li; Minling Wang; Xiaobo Tian; Yun Chen; Tao Xu; et al. (Science Bulletin, 2023)

Attribution analysis of non-stationary hydrological drought using the GAMLSS framework and an improved SWAT model - Youxin Wang; Tao Peng; Yanhu He; Vijay P. Singh; Qingxia Lin; Xiaohua Dong; Tianyi Fan; Ji Liu; Jiali Guo; Gaoxu Wang (Journal of Hydrology, 2023)

Intimately tracking NO2 pollution over the New York City - Long Island Sound land-water continuum: An integration of shipboard, airborne, satellite observations, and models - Maria Tzortziou; Christopher P. Loughner; Daniel L. Goldberg; Laura Judd; Dilchand Nauth; Charlotte F. Kwong; Tong Lin; Alexander Cede; Nader Abuhassan (Science of The Total Environment, 2023)

Use of reconstituted kefir consortia to determine the impact of microbial composition on kefir metabolite profiles - Benjamin C.T. Bourrie; Natalie Diether; Ryan P. Dias; Seo Lin Nam; A. Paulina de la Mata; Andrew J. Forgie; Gautam Gaur; James J. Harynuk; Michael Gänzle; Paul D. Cotter; Benjamin P. Willing (Food Research International, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

RETRACTED: Boron contamination and its risk management in terrestrial and aquatic environmental settings - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2023)

Impact of extreme climatic events on the total suspended matter concentrations in coastal waters using OceanSat-2 observations - Sravanthi Nukapothula; Ali P. Yunus; Chen Chuqun; Xiayan Lin (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Did Early Pleistocene hominins control hammer strike angles when making stone tools? - Li Li; Jonathan S. Reeves; Sam C. Lin; David R. Braun; Shannon P. McPherron (Journal of Human Evolution, 2023)

Cloud condensation nuclei activation properties of Mediterranean pollen types considering organic chemical composition and surface tension effects - A. Casans; F. Rejano; J. Maldonado-Valderrama; J.A. Casquero-Vera; S. Ruiz-Peñuela; B.L. van Drooge; H. Lyamani; A. Cazorla; E. Andrews; Jack J. Lin; F. Mirza-Montoro; D. Pérez-Ramírez; et al. (Atmospheric Environment, 2023)

Characterization of fouled ultrafiltration membranes from a full-scale wastewater reclamation plant in iron and steel industry - P.-H. Lin; Y.-C. Su; C.-L. Chen; I.-Y. Tsao (International Journal of Environmental Science and Technology, 2023)

Novel ternary Cu0-coupled core-shell Fe0/C nanoparticles micro-electrolysis system toward degradation of organic pollutants: Synergistic effects and removal mechanism - Lin Niu; Xiaoli Zhao; Zhi Tang; Yaqi Cai; Qitao Lei; Deyi Hou; Hongyun Niu; Liangjie Wang; John P. Giesy; Fengchang Wu (Science of The Total Environment, 2023)

Physiological responses and antioxidant properties of spiny coriander (Eryngium foetidum L.) under shading and nitrogen fertilization - Renê A. S. Campos; Santino Seabra Júnior; Gabriela G. Gonçalves; Franciele da S. Ponce; Ana Claudia Macedo; Chau Ming Lin; Giuseppina P. P. Lima (Acta Physiologiae Plantarum, 2023)

A CMIP6-based framework for propagation from meteorological and hydrological droughts to socioeconomic drought - Tian Wang; Xinjun Tu; Vijay P Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou; Jinglei Zhu (Journal of Hydrology, 2023)

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

Contrasting patterns and controls of soil carbon and nitrogen isotope compositions in coastal wetlands of China - Shaopan Xia; Zhaoliang Song; Bhupinder Pal Singh; Laodong Guo; Nanthi Bolan; Weiqi Wang; Guanghui Lin; Yin Fang; Xuefa Wen; Jing Wang; Iain P. Hartley; Xueyan Liu; et al. (Plant and Soil, 2023)

Novel perfluoroalkyl substances (PFAS) discovered in whole blood using automated non-targeted analysis of dried blood spots - Jeremy P. Koelmel; Elizabeth Z. Lin; Emily Parry; Paul Stelben; Emma E. Rennie; Krystal J. Godri Pollitt (Science of The Total Environment, 2023)

Bipolar ice-core records constrain possible dates and global radiative forcing following the ∼74 ka Toba eruption - Jiamei Lin; Peter M. Abbott; Michael Sigl; Jørgen P. Steffensen; Robert Mulvaney; Mirko Severi; Anders Svensson (Quaternary Science Reviews, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Bivariate socioeconomic drought assessment based on a hybrid framework and impact of human activities - Zonglin Zhou; Xinjun Tu; Tian Wang; Vijay P. Singh; Xiaohong Chen; Kairong Lin (Journal of Cleaner Production, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Metabolic pathways altered by air pollutant exposure in association with lipid profiles in young adults - Jiawen Liao; Jesse Goodrich; Douglas I. Walker; Yan Lin; Fred Lurmann; Chenyu Qiu; Dean P. Jones; Frank Gilliland; Lida Chazi; Zhanghua Chen (Environmental Pollution, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Characteristics and correlation of soil low-molecular-weight organic acids and nutrients in four plantations in red soil area of south China - Y. M. Ren; Z. J. Hou; T. Su; Z. R. Lin; A. Q. Liu; L. P. Cai (International Journal of Environmental Science and Technology, 2023)

Solubility controls on plutonium and americium release in subsurface environments exposed to acidic processing wastes - Hilary P. Emerson; Sergey I. Sinkov; Carolyn I. Pearce; Kirk J. Cantrell; Calvin H. Delegard; Michelle M.V. Snyder; May-Lin Thomas; Dallas D. Reilly; Edgar C. Buck; Lucas E. Sweet; Amanda J. Casella; Jennifer C. Carter; et al. (Applied Geochemistry, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Abatement technologies for copper containing industrial wastewater effluents – A review - Jayson Sime D. Jeremias; Jui-Yen Lin; Maria Lourdes P. Dalida; Ming-Chun Lu (Journal of Environmental Chemical Engineering, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Progerin induces a phenotypic switch in vascular smooth muscle cells and triggers replication stress and an aging-associated secretory signature - Nuria Coll-Bonfill; Urvashi Mahajan; Elena V. Shashkova; Chien-Jung Lin; Robert P. Mecham; Susana Gonzalo (GeroScience, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Hemicellulose-bacterial cellulose ribbon interactions affect the anisotropic mechanical behaviour of bacterial cellulose hydrogels - Si-Qian Chen; Patricia Lopez-Sanchez; Deirdre Mikkelsen; Marta Martinez-Sanz; Zhaofeng Li; Shuyan Zhang; Elliot P. Gilbert; Lin Li; Michael J. Gidley (Food Hydrocolloids, 2023)

Metabolic reprogramming of Helicoverpa armigera larvae by HearNPV facilitates viral replication and host immune suppression - Zhiqiang Tian; Lin Zhu; J. P. Michaud; Meng Zha; Jie Cheng; Zhongjian Shen; Xiaoming Liu; Xiaoxia Liu (Molecular Ecology, 2023)
Baculoviruses are highly evolved parasites that genetically reprogram the developing phenotype of their host insect to produce a vessel for virus replication and dispersal. Here we show that larvae of Helicoverpa armigera infected with HearNPV accumulate glucose in the midgut, which reduces food consumption and alters the dynamics of pathways governing metabolism and immunity. We used transcriptomics to demonstrate the role of the insulin signalling pathway in regulating the HearNPV infection process. Dietary restriction decreased mortality of infected larvae and reduced viral replication prior to death, whereas dietary supplementation with glucose produced the opposite effects. The expression of most tricarboxylic acid cycle (TCA) and energy metabolism‐related genes was reduced in infected larvae, whereas the expression of immunity‐, glycolysis‐ and insulin‐related genes was enhanced. Treatment of infected larvae with insulin increased their survival, reduced viral replication and inhibited climbing behaviour compared to a control treatment with DMSO, whereas RNAi suppression of the insulin receptor gene produced the opposite effects. Inhibition of glycolysis with dichloroacetate (DCA) promoted viral replication and accelerated larval death, but inhibition of the TCA cycle with 2‐deoxyglucose (2‐DG) did not, although both diminished climbing behaviour. This work demonstrates that successful baculovirus infections hinge on metabolic reprogramming of the host and concurrent suppression of immune responses in the larval midgut, with the insulin signalling pathway mediating a trade‐off between glucose metabolism and virus resistance.

Wearable Passive Samplers for Assessing Environmental Exposure to Organic Chemicals: Current Approaches and Future Directions - Joseph O. Okeme; Jeremy P. Koelmel; Emily Johnson; Elizabeth Z. Lin; Dong Gao; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2023)

Assessment of future socioeconomic drought based on CMIP6: evolution, driving factors and propagation - Tian Wang; Xinjun Tu; Vijay P. Singh; Xiaohong Chen; Kairong Lin; Zonglin Zhou; Yin Tan (Journal of Hydrology, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Microplastic contamination in coral reef fishes and its potential risks in the remote Xisha areas of the South China Sea - Lei Huang; Qian P. Li; Hengxiang Li; Lang Lin; Xiangrong Xu; Xiaojie Yuan; Jayamini B. Koongolla; Huawei Li (Marine Pollution Bulletin, 2023)

Non-essential and essential trace element mixtures and kidney function in early pregnancy – A cross-sectional analysis in project viva - Pi-I.D. Lin; Andres Cardenas; Sheryl L. Rifas-Shiman; Ami R. Zota; Marie-France Hivert; Izzuddin M. Aris; Alison P. Sanders (Environmental Research, 2023)

A comprehensive review on water stable metal-organic frameworks for large-scale preparation and applications in water quality management based on surveys made since 2015 - R. Y. Li; Z. S. Wang; Z. Y. Yuan; Constance Van Horne; Viatcheslav Freger; M. Lin; R. K. Cai; J. P. Chen (Critical Reviews in Environmental Science and Technology, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Hydrological drought dynamics and its teleconnections with large-scale climate indices in the Xijiang River basin, South China - Qingxia Lin; Zhiyong Wu; Jingjing Liu; Vijay P. Singh; Zheng Zuo (Theoretical and Applied Climatology, 2022)

Trends in Chlorophyll-a Concentration Along the Krishna–Godavari Basin as Observed From MODIS Archives - Sravanthi Nukapothula; Chuqun Chen; Ali P. Yunus; Xiayan Lin (Pure and Applied Geophysics, 2022)

Methods to control harmful algal blooms: a review - Barathan Balaji-Prasath; Ying Wang; Yu Ping Su; David P. Hamilton; Hong Lin; Luwei Zheng; Yong Zhang (Environmental Chemistry Letters, 2022)

Coastal upwelling enhances abundance of a symbiotic diazotroph (UCYN-A) and its haptophyte host in the Arctic Ocean - Corday R. Selden; Sveinn V. Einarsson; Kate E. Lowry; Katherine E. Crider; Robert S. Pickart; Peigen Lin; Carin J. Ashjian; P. Dreux Chappell (Frontiers in Marine Science, 2022)
The apparently obligate symbiosis between the diazotroph Candidatus Atelocyanobacterium thalassa (UCYN-A) and its haptophyte host, Braarudosphaera bigelowii , has recently been found to fix dinitrogen (N 2 ) in polar waters at rates (per cell) comparable to those observed in the tropical/subtropical oligotrophic ocean basins. This study presents the novel observation that this symbiosis increased in abundance during a wind-driven upwelling event along the Alaskan Beaufort shelfbreak. As upwelling relaxed, the relative abundance of B. bigelowii among eukaryotic phytoplankton increased most significantly in waters over the upper slope. As the host’s nitrogen demands are believed to be supplied primarily by UCYN-A, this response suggests that upwelling may enhance N 2 fixation as displaced coastal waters are advected offshore, potentially extending the duration of upwelling-induced phytoplankton blooms. Given that such events are projected to increase in intensity and number with ocean warming, upwelling-driven N 2 fixation as a feedback on climate merits investigation.

A 2019 Outbreak Investigation of Hepatitis A Virus Infections in the United States Linked to Imported Fresh Blackberries - Monica McClure; Johnson Nsubuga; Martha P. Montgomery; Erin Jenkins; Alvin Crosby; Daniela Schoelen; Colin Basler; Sumathi Ramachandran; Yulin Lin; Guo-liang Xia; Yury Khudaykov; Vilasini Suktankar; et al. (Food and Environmental Virology, 2022)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Quantifying knapping actions: a method for measuring the angle of blow on flakes - Li Li; Jonathan S. Reeves; Sam C. Lin; Claudio Tennie; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2022)
Stone artifacts are critical for investigating the evolution of hominin behavior—they are among our only proxies for hominin behavior in deep time. Hominin cognition and skill are often inferred by reconstructing the technical decisions hominins made throughout the knapping process. However, despite many advancements in understanding how hominins knapped, some of the key factors involved in past flake production cannot be easily/readily derived from stone artifacts. In particular, the angle at which the knapper strikes the hammer against the core to remove the flake, or the angle of blow, is a key component of the knapping process that has up to now remained unmeasurable on archeological assemblages. In this study, we introduce a new method for estimating the angle of blow from the ventral surface of flakes. This method was derived from a controlled experiment that explicitly connects fracture mechanics to flake variability. We find that a feature of the flake’s bulb of percussion, what we call the bulb angle, is a measurable indicator of the angle of blow. Our experimental finding is further validated in two additional datasets from controlled and replicative knapping experiments. These results demonstrate the utility of continuing to link flake variation with technical decision-making to fracture mechanics. In addition, they also provide a useful and relatively simple means to capture a currently invisible aspect of hominin stone tool production behavior.

Ocean acidification in the Western Pacific: Boron isotopic composition recorded in a tropical massive coral core from Lanyu Islet SE Taiwan - Chen-Feng You; P-Y. Lin; Kuo-Fang Huang; Chuan-Hsiung Chung; Zhifei Liu (Frontiers in Marine Science, 2022)
Boron (B) and B isotopic compositions (δ 11 B) in biogenic carbonates are useful proxies for pH reconstruction in the ocean. However, high-resolution archives are scarce due to associated sampling and analytical difficulty. In this study, a modern long-lived massive coral skeleton ( Porites lobata ) from Lanyu Islet off southeast Taiwan was drilled and used for high-resolution major/trace element analyses, including trace elements B and δ 11 B, as well as oxygen and carbon isotopes, to investigate the associated environmental changes during 1991–1997. To avoid complicated biological influence, the top-most tissue layer was excluded in this study. The coralline records show a clear temporal trend in metal/Ca-based sea surface temperatures (SSTs) on annual and monthly timescales. In particular, the Mg/Ca-SSTs, the most sensitive temperature proxy at the site, show a significant warming trend (+0.2°C year −1 ) during the study period. On the other hand, subtle changes in the annual δ 11 B record were identified, corresponding to ~0.2 pH unit, which is comparable with other coral records in the Pacific, e.g., the South China Sea (SCS), Guam Island, Flinders, and Arlington Reef, as well as the in-situ seawater pH measurement at Hawaii station. This corresponds to an acidification rate of ~0.25 pH unit 100 year −1 , similar to other coralline data, in-situ pH/pCO 2 measurement, or model predictions, and emphasizes the importance of ocean acidification due to anthropogenic activities. Combined with the Mg/Ca-SST, the intra-annual data show a clear seasonal cycle with higher pH in winter, consistent with the pCO 2 at the oceanic surface. These chemical and isotopic results in corals conclude that marine biogenic carbonates are informative for oceanic pH reconstruction and can provide new insights into the relationships between climate changes and environmental responses on the coast of Taiwan.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Angiopoietin-Like Protein 4 Is Involved in Manganese Superoxide Dismutase-Mediated Suppression of Breast Cancer Cell Growth - P. Li; X. Zeng; Y. Liu; M. Lin (Bulletin of Experimental Biology and Medicine, 2022)

A New Non-stationary Hydrological Drought Index Encompassing Climate Indices and Modified Reservoir Index as Covariates - Youxin Wang; Tao Peng; Qingxia Lin; Vijay P. Singh; Xiaohua Dong; Chen Chen; Ji Liu; Wenjuan Chang; Gaoxu Wang (Water Resources Management, 2022)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Baculoviruses hijack the visual perception of their caterpillar hosts to induce climbing behaviour thus promoting virus dispersal - Xiaoming Liu; Zhiqiang Tian; Limei Cai; Zhongjian Shen; J. P. Michaud; Lin Zhu; Shuo Yan; Vera I. D. Ros; Kelli Hoover; Zhen Li; Songdou Zhang; Xiaoxia Liu (Molecular Ecology, 2022)
Baculoviruses can induce climbing behaviour in their caterpillar hosts to ensure they die at elevated positions to enhance virus transmission, providing an excellent model to study parasitic manipulation of host behaviour. Here, we demonstrate that climbing behaviour occurred mostly during daylight hours, and that the height at death of Helicoverpa armigera single nucleopolyhedrovirus (HearNPV)‐infected larvae increases with the height of the light source. Phototaxic and electroretinogram (ERG) responses were enhanced after HearNPV‐infection in host larvae, and ablation of stemmata in infected larvae prevented both phototaxis and climbing behaviour. Through transcriptome and quantitative PCR, we confirmed that two opsin genes (a blue light‐sensitive gene, HaBL ; and a long wave‐sensitive gene, HaLW ) as well as the TRPL (transient receptor potential‐like channel protein) gene, all integral to the host's visual perception pathway, were significantly upregulated after HearNPV infection. Knockout of HaBL , HaLW , or TRPL genes using the CRISPR/Cas9 system resulted in significantly reduced ERG responses, phototaxis, and climbing behaviour in HearNPV‐infected larvae. These results reveal that HearNPV alters the expression of specific genes to hijack host visual perception at fundamental levels—photoreception and phototransduction—in order to induce climbing behaviour in host larvae.

Large quantities of small microplastics permeate the surface ocean to abyssal depths in the South Atlantic Gyre - Shiye Zhao; Erik R. Zettler; Ryan P. Bos; Peigen Lin; Linda A. Amaral‐Zettler; Tracy J. Mincer (Global Change Biology, 2022)
Hundreds of studies have surveyed plastic debris in surface ocean gyre and convergence zones, however, comprehensive microplastics (MPs, ≤5 mm) assessments beneath these surface accumulation areas are lacking. Using in situ high‐volume filtration, Manta net and MultiNet sampling, combined with micro‐Fourier‐transform‐infrared imaging, we discovered a high abundance (up to 244.3 pieces per cubic meter [n m −3 ]) of small microplastics (SMPs, characteristically 300 μm) concurrently collected in MultiNet samples. Higher‐density polymers (e.g., alkyd resins and polyamide) comprised >65% of the total pump sample count, highlighting a discrepancy between polymer compositions from previous ocean surface‐based surveys, typically dominated by buoyant polymers such as polyethylene and polypropylene. Contrary to previous reports stating LMP preferentially accumulated at density gradients, SMP with presumably slower sinking rates are much less influenced by density gradients, thus resulting in a more even vertical distribution in the water column, and potentially longer residence times. Overall, our findings suggest that SMP is a critical and largely underexplored constituent of the oceanic plastic inventory. Additionally, our data support that weak current systems contribute to the formation of SMP hotspots at depth, implying a higher encounter rate for subsurface particle feeders. Our study unveils the prevalence of plastics in the entire water column, highlighting the urgency for more quantification of the deep‐ocean MP, particularly the smaller size fraction, to better understand ecosystem exposure and to predict MP fate and impacts.

Warming effects on grassland productivity depend on plant diversity - Junjiong Shao; Xuhui Zhou; Kees Jan van Groenigen; Guiyao Zhou; Huimin Zhou; Lingyan Zhou; Meng Lu; Jianyang Xia; Lin Jiang; Bruce A. Hungate; Yiqi Luo; Fangliang He; et al. (Global Ecology and Biogeography, 2022)
Aim Climate warming and biodiversity loss both alter plant productivity, yet we lack an understanding of how biodiversity regulates the responses of ecosystems to warming. In this study, we examine how plant diversity regulates the responses of grassland productivity to experimental warming using meta‐analytic techniques. Location Global. Major taxa studied Grassland ecosystems. Methods Our meta‐analysis is based on warming responses of 40 different plant communities obtained from 20 independent studies on grasslands across five continents. Results Our results show that plant diversity and its responses to warming were the most important factors regulating the warming effects on plant productivity, among all the factors considered (plant diversity, climate and experimental settings). Specifically, warming increased plant productivity when plant diversity (indicated by effective number of species) in grasslands was lower than 10, whereas warming decreased plant productivity when plant diversity was greater than 10. Moreover, the structural equation modelling showed that the magnitude of warming enhanced plant productivity by increasing the performance of dominant plant species in grasslands of diversity lower than 10. The negative effects of warming on productivity in grasslands with plant diversity greater than 10 were partly explained by diversity‐induced decline in plant dominance. Main conclusions Our findings suggest that the positive or negative effect of warming on grassland productivity depends on how biodiverse a grassland is. This may mainly be due to differences in how warming may affect plant dominance and subsequent shifts in interspecific interactions in grasslands of different plant diversity levels.

Hereditary cancer panel testing challenges and solutions for the latinx community: costs, access, and variants - Michael P. Douglas; Grace A. Lin; Julia R. Trosman; Kathryn A. Phillips (Journal of Community Genetics, 2022)
Hereditary breast and ovarian cancers (HBOCs) are common among the Latinx population, and risk testing is recommended using multi-gene hereditary cancer panels (HCPs). However, little is known about how payer reimbursement and out-of-pocket expenses impact provider ordering of HCP in the Latinx population. Our objective is to describe key challenges and possible solutions for HCP testing in the Latinx population. As part of a larger study, we conducted semi-structured interviews with key provider informants (genetic counselors, oncologist, nurse practitioner) from safety-net institutions in the San Francisco Bay Area. We used a deductive thematic analysis approach to summarize themes around challenges and possible solutions to facilitating HCP testing in Latinx patients. We found few financial barriers for HCP testing for the Latinx population due to laboratory patient assistance programs that cover testing at low or no cost to patients. However, we found potential challenges related to the sustainability of low-cost testing and out-of-pocket expenses for patients, access to cascade testing for family members, and pathogenic variants specific to Latinx. Providers questioned whether current laboratory payment programs that decrease barriers to testing are sustainable and suggested solutions for accessing cascade testing and ensuring variants specific to the Latinx population were included in testing. The use of laboratories with payment assistance programs reduces barriers to HCP testing among the US population; however, other barriers are present that may impact testing use in the Latinx population and must be addressed to ensure equitable access to HCP testing for this population.

REPIMPACT - a prospective longitudinal multisite study on the effects of repetitive head impacts in youth soccer - Inga K. Koerte; Roald Bahr; Peter Filipcik; Jolien Gooijers; Alexander Leemans; Alexander P. Lin; Yorghos Tripodis; Martha E. Shenton; Nir Sochen; Stephan P. Swinnen; Ofer Pasternak (Brain Imaging and Behavior, 2022)
Repetitive head impacts (RHI) are common in youth athletes participating in contact sports. RHI differ from concussions; they are considered hits to the head that usually do not result in acute symptoms and are therefore also referred to as “subconcussive” head impacts. RHI occur e.g., when heading the ball or during contact with another player. Evidence suggests that exposure to RHI may have cumulative effects on brain structure and function. However, little is known about brain alterations associated with RHI, or about the risk factors that may lead to clinical or behavioral sequelae. REPIMPACT is a prospective longitudinal study of competitive youth soccer players and non-contact sport controls aged 14 to 16 years. The study aims to characterize consequences of exposure to RHI with regard to behavior (i.e., cognition, and motor function), clinical sequelae (i.e., psychiatric and neurological symptoms), brain structure, function, diffusion and biochemistry, as well as blood- and saliva-derived measures of molecular processes associated with exposure to RHI (e.g., circulating microRNAs, neuroproteins and cytokines). Here we present the structure of the REPIMPACT Consortium which consists of six teams of clinicians and scientists in six countries. We further provide detailed information on the specific aims and the design of the REPIMPACT study. The manuscript also describes the progress made in the study thus far. Finally, we discuss important challenges and approaches taken to overcome these challenges.

Mycorrhizal associations of tree species influence soil nitrogen dynamics via effects on soil acid–base chemistry - Guigang Lin; Matthew E. Craig; Insu Jo; Xugao Wang; De‐Hui Zeng; Richard P. Phillips (Global Ecology and Biogeography, 2022)
Aim Plants and their associated microbes influence nutrient cycling in terrestrial ecosystems, yet we have a limited understanding of how soil acidity mediates the process. Here, we investigate whether reported differences in nitrogen (N) cycling between forests dominated by arbuscular mycorrhizal (AM) trees and ectomycorrhizal (ECM) trees are related to changes in soil acid–base chemistry induced by mycorrhizal associations. Location Global. Time period 1969–2018. Major taxa studied Trees. Methods We measured and synthesized variables of leaf litter quality, soil acid–base chemistry and N cycling from: (1) a landscape‐scale study of 230 subplots varying widely in AM tree dominance in a 25 ha forest plot; (2) a regional‐scale study of 40 AM‐ and 56 ECM‐dominated plots in 10 temperate forests across the eastern USA; (3) a continental‐scale study of > 3,000 forest plots from 10 ecoregions across the contiguous USA; and (4) a global meta‐analysis of 105 study sites with co‐occurring AM and ECM forest stands. Results Across all spatial scales, ECM‐dominated forests were associated with greater soil acidity. In particular, ECM‐dominated soils exhibited lower soil pH and base cations, although the magnitude of mycorrhizal‐associated differences in soil acid–base chemistry depended on the biomes, with differences being more pronounced in temperate than in sub/tropical forests. Higher lignin and lower base cations in ECM tree leaf litter were related to greater soil acidity in ECM‐dominated forests. Moreover, the lower inorganic N concentrations and slower N transformation rates in ECM‐dominated forests were associated with their greater soil acidity. Main conclusions Our results indicate that the scale‐invariant feedbacks between plant nutrient‐use strategies and soil properties have the potential to impact forest community assembly and ecosystem processes, particularly in the context of global change.

Genetic dissection of a pericentromeric region of barley chromosome 6H associated with Fusarium head blight resistance, grain protein content and agronomic traits - Yadong Huang; Lu Yin; Ahmad H. Sallam; Shane Heinen; Lin Li; Karen Beaubien; Ruth Dill-Macky; Yanhong Dong; Brian J. Steffenson; Kevin P. Smith; Gary J. Muehlbauer (Theoretical and Applied Genetics, 2021)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Prevalence and Implications of Per- and Polyfluoroalkyl Substances (PFAS) in Settled Dust - Tina Savvaides; Jeremy P. Koelmel; Yakun Zhou; Elizabeth Z. Lin; Paul Stelben; Juan J. Aristizabal-Henao; John A. Bowden; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Developing urinary pyrrole–amino acid adducts as non-invasive biomarkers for identifying pyrrolizidine alkaloids-induced liver injury in human - Lin Zhu; Chunyuan Zhang; Wei Zhang; Qingsu Xia; Jiang Ma; Xin He; Yisheng He; Peter P. Fu; Wei Jia; Yuzheng Zhuge; Ge Lin (Archives of Toxicology, 2021)

Structural basis for the functional properties of the P2X7 receptor for extracellular ATP - Lin-Hua Jiang; Emily A. Caseley; Steve P. Muench; Sébastien Roger (Purinergic Signalling, 2021)
The P2X7 receptor, originally known as the P2Z receptor due to its distinctive functional properties, has a structure characteristic of the ATP-gated ion channel P2X receptor family. The P2X7 receptor is an important mediator of ATP-induced purinergic signalling and is involved the pathogenesis of numerous conditions as well as in the regulation of diverse physiological functions. Functional characterisations, in conjunction with site-directed mutagenesis, molecular modelling, and, recently, structural determination, have provided significant insights into the structure–function relationships of the P2X7 receptor. This review discusses the current understanding of the structural basis for the functional properties of the P2X7 receptor.

Legal Issues for Artificial Floating Islands - Maarten M. B. Flikkema; Fen-Yu (Vicky) Lin; Pernille P. J. van der Plank; Jos Koning; Olaf Waals (Frontiers in Marine Science, 2021)
Developments of multi-use floating islands are accelerated by an increase in offshore activities and pressing needs to create extra space in coastal regions for the surging population. The Horizon 2020 EU funded research project Space@Sea developed a modular floating island concept for offshore multi-use applications and examined current legal issues and barriers concerning its development. In this paper a floating island is defined to be “an artificially created floater, or set of connected floaters, moored to the seabed of which the topside can be used for activities similar to activities on land”. This paper aims to delve into governance issues like the assignment of authority on a multi-use floating island and the shift from regulating offshore living for working purposes to living purposes, as well as maritime law and property law (using the Netherlands as case study). Within the Exclusive Economic Zone (EEZ) a coastal state can establish, locate, and govern the floating island. For the high seas the International Maritime Organization (IMO) is the most probable organization to initiate a discussion on settlement of floating islands. For each activity on the floating island, limiting criteria regarding motions as well as safety rules and regulations need to be established. Industry and housing will have completely different requirements regarding safety which will not be possible to fit in a one size fits all regulation. This case study shows that current Dutch property law prohibit the division of ownership of buildings built on floating objects. They can only be owned together as one object. For urban expansion, future inhabitants will want to have the possibility to buy property, requiring an amendment of current property law. It is to be expected that other countries will have similar or additional governance challenges. The Space@Sea project has developed a technical solution for floating islands which have identified barriers for multi-use in the rules and regulations described in this paper. The paper urges the responsible institutions and stakeholders to take on their roles in overcoming these barriers.

Hidden in plain sight: a molecular field survey of three wheat leaf blotch fungal diseases in North-Western Europe shows co-infection is widespread - Annemarie Fejer Justesen; Beatrice Corsi; Andrea Ficke; Lorenz Hartl; Sarah Holdgate; Lise Nistrup Jørgensen; Morten Lillemo; Min Lin; Ian J. Mackay; Volker Mohler; Melanie Stadlmeier; Kar-Chun Tan; et al. (European Journal of Plant Pathology, 2021)
Wheat ( Triticum aestivum L.) yields are commonly affected by foliar infection by fungal pathogens. Of these, three wheat leaf blotch fungal diseases, septoria nodorum blotch (SNB), tan spot (TS) and septoria tritici blotch (STB), caused by Parastagonospora nodorum ( Pn ), Pyrenophora tritici-repentis ( Ptr ) and Zymoseptoria tritici ( Zt ), respectively, induce major yield losses. Infection results in necrotic areas on the leaf, and it is often difficult to determine the underlying causative pathogen from visible symptoms alone, especially in mixed infections. Here, a regional survey of 330 wheat samples collected across three seasons (years 2015–2017) from four north-west European countries was undertaken. Using quantitative polymerase chain reaction (qPCR) assays specific for each pathogen, as well as disease assessment of leaf materials, distinct regional differences were identified. Two-thirds (65%) of all samples harbored at least two of the three pathogens. Norway had high SNB abundance, but also showed mixed infections of SNB, TS and STB. In Germany, TS was prevalent, with STB also common. Danish samples commonly possessed all three pathogens, with STB prevalent, followed by TS and SNB. The UK had a major prevalence of STB with minimal occurrence of TS and SNB. Across all samples, qPCR identified Zt , Pn and Ptr in 90%, 54% and 57% of samples, respectively. For each pathogen, average disease levels via visual assessment showed modest positive correlation with fungal DNA concentrations (R 2 = 0.13–0.32). Overall, our study highlights that the occurrence of mixed infection is common and widespread, with important implications for wheat disease management and breeding strategies.

Genetics of mouse behavioral and peripheral neural responses to sucrose - Cailu Lin; Masashi Inoue; Xia Li; Natalia P. Bosak; Yutaka Ishiwatari; Michael G. Tordoff; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

Genetic controls of Tas1r3-independent sucrose consumption in mice - Cailu Lin; Michael G. Tordoff; Xia Li; Natalia P. Bosak; Masashi Inoue; Yutaka Ishiwatari; Longhui Chen; Gary K. Beauchamp; Alexander A. Bachmanov; Danielle R. Reed (Mammalian Genome, 2021)

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Use of Exposomic Methods Incorporating Sensors in Environmental Epidemiology - Brett T. Doherty; Jeremy P. Koelmel; Elizabeth Z. Lin; Megan E. Romano; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2021)

Machine learning prediction of neurocognitive impairment among people with HIV using clinical and multimodal magnetic resonance imaging data - Yunan Xu; Yizi Lin; Ryan P. Bell; Sheri L. Towe; John M. Pearson; Tauseef Nadeem; Cliburn Chan; Christina S. Meade (Journal of NeuroVirology, 2021)

Fine-scale roadkill risk models: understanding the intersection of wildlife and roads - Kristina Chyn; Te-En Lin; David P. Wilkinson; James L. Tracy; A. Michelle Lawing; Lee A. Fitzgerald (Biodiversity and Conservation, 2021)

Contribution of Val/Ile87 residue in the extracellular domain in agonist-induced current responses of the human and rat P2X7 receptors - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2020)
The P2X7 receptor (P2X7R) is an ATP-gated cation channel with a critical role in many physiological and pathological processes, and shows prominent functional differences across mammalian species, exemplified by larger current responses of the rat (r) P2X7R to ATP and its analogue BzATP and a greater sensitivity to agonists compared with the human (h) P2X7R. Here, we showed that substitution of Val87 residue in the extracellular domain of the hP2X7R with isoleucine in the rP2X7R increased the current responses of the hP2X7R to both ATP and BzATP. Conversely, introduction of reciprocal I87V mutation in the rP2X7R led to a noticeable but statistically insignificant reduction in the current responses of the rP2X7R to ATP and BzATP. The mutations did not affect the sensitivity of the human and rat P2X7Rs to ATP and BzATP. These results suggest a contribution of Val/Ile87 in agonist-induced current responses of human and rat P2X7Rs, which helps to better understand the molecular determinants for species-dependent function of the mammalian P2X7Rs.

Exposure to a high dose of amoxicillin causes behavioral changes and oxidative stress in young zebrafish - Cinara L. Gonçalves; Francine F. P. Vasconcelos; Leticia B. Wessler; Isabela S. Lemos; Gabriela Candiotto; Jaime Lin; Mariane B. D. Matias; Eduardo P. Rico; Emilio L. Streck (Metabolic Brain Disease, 2020)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Correction to: Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2020)
After publication in volume [37], issue [1], page [94–101] the authors decided to opt for Open Choice and to make the article an open access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2018 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/), which permits use, duplication, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Waiting and “weighted down”: the challenge of anticipatory loss for individuals and families with Li-Fraumeni Syndrome - Allison Werner-Lin; Jennifer L. Young; Catherine Wilsnack; Shana L. Merrill; Victoria Groner; Mark H. Greene; Payal P. Khincha (Familial Cancer, 2020)

Non-Invasive Quantification of Ventricular Contractility, Arterial Elastic Function and Ventriculo-Arterial Coupling from a Single Diagnostic Encounter Using Simultaneous Arterial Tonometry and Magnetic Resonance Imaging - Mayooran Namasivayam; Audrey Adji; Linda Lin; Christopher S. Hayward; Michael P. Feneley; Michael F. O’Rourke; David W. M. Muller; Andrew Jabbour (Cardiovascular Engineering and Technology, 2020)

Developing quantitative PCR assays to detect threatened and invasive freshwater turtles in Hong Kong using environmental DNA - Ivan P. Y. Lam; Yik-Hei Sung; Liu Lin; Jonathan J. Fong (Conservation Genetics Resources, 2020)

Formation mechanism of a rainfall triggered complex landslide in southwest China - Qiu-xiang Huang; Xiang-tao Xu; P. H. S. W. Kulatilake; Feng Lin (Journal of Mountain Science, 2020)

A deep-level region-based visual representation architecture for detecting strawberry flowers in an outdoor field - P. Lin; W. S. Lee; Y. M. Chen; N. Peres; C. Fraisse (Precision Agriculture, 2020)

A new slice-based method for calculating the minimum safe thickness for a filled-type karst cave - Z. H. Xu; X. Huang; S. C. Li; P. Lin; X. S. Shi; J. Wu (Bulletin of Engineering Geology and the Environment, 2020)

Potential changes to the biology and challenges to the management of invasive sea lamprey Petromyzon marinus in the Laurentian Great Lakes due to climate change - Robert J. Lennox; Gale A. Bravener; Hsien‐Yung Lin; Charles P. Madenjian; Andrew M. Muir; Christina K. Remucal; Kelly F. Robinson; Andrew M. Rous; Michael J. Siefkes; Michael P. Wilkie; Daniel P. Zielinski; Steven J. Cooke (Global Change Biology, 2020)
Control programs are implemented to mitigate the damage caused by invasive species worldwide. In the highly invaded Great Lakes, the climate is expected to become warmer with more extreme weather and variable precipitation, resulting in shorter iced‐over periods and variable tributary flows as well as changes to pH and river hydrology and hydrogeomorphology. We review how climate change influences physiology, behavior, and demography of a damaging invasive species, sea lamprey ( Petromyzon marinus ), in the Great Lakes, and the consequences for sea lamprey control efforts. Sea lamprey control relies on surveys to monitor abundance of larval sea lamprey in Great Lakes tributaries. The abundance of parasitic, juvenile sea lampreys in the lakes is calculated by surveying wounding rates on lake trout ( Salvelinus namaycush ), and trap surveys are used to enumerate adult spawning runs. Chemical control using lampricides (i.e., lamprey pesticides) to target larval sea lamprey and barriers to prevent adult lamprey from reaching spawning grounds are the most important tools used for sea lamprey population control. We describe how climate change could affect larval survival in rivers, growth and maturation in lakes, phenology and the spawning migration as adults return to rivers, and the overall abundance and distribution of sea lamprey in the Great Lakes. Our review suggests that Great Lakes sea lamprey may benefit from climate change with longer growing seasons, more rapid growth, and greater access to spawning habitat, but uncertainties remain about the future availability and suitability of larval habitats. Consideration of the biology of invasive species and adaptation of the timing, intensity, and frequency of control efforts is critical to the management of biological invasions in a changing world, such as sea lamprey in the Great Lakes.

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

Castor patatin-like phospholipase A IIIβ facilitates removal of hydroxy fatty acids from phosphatidylcholine in transgenic Arabidopsis seeds - Yingyu Lin; Guanqun Chen; Elzbieta Mietkiewska; Ziliang Song; Kristian Mark P. Caldo; Stacy D. Singer; John Dyer; Mark Smith; Thomas McKeon; Randall J. Weselake (Plant Molecular Biology, 2019)

Characteristics and distribution of clay minerals and their effects on reservoir quality: Huagang Formation in the Xihu Sag, East China Sea Basin - X. L. Sun; C. Y. Lin; X. G. Zhang; J. L. Lin; Z. X. Zhao; D. W. Huang; D. P. Duan (Australian Journal of Earth Sciences, 2019)

The Contributions of Individual Muscle–Tendon Units to the Plantarflexor Group Force–Length Properties - Mehrdad Javidi; Craig P. McGowan; David C. Lin (Annals of Biomedical Engineering, 2019)

Mechanism of Microstructural Variation Under Cyclic Shearing of Shantou Marine Clay: Experimental Investigation and Model Development - P. Lin; Raval Ratnam; Hima Sankari; A. Garg (Geotechnical and Geological Engineering, 2019)

Coalescence Models Reveal the Rise of the White-Bellied Rat (Niviventer confucianus) Following the Loss of Asian Megafauna - Deyan Ge; Liang Lu; Alexei V. Abramov; Zhixin Wen; Jilong Cheng; Lin Xia; Alfried P. Vogler; Qisen Yang (Journal of Mammalian Evolution, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Time-dependent shake map for Uttarakhand Himalayas, India, using recorded earthquakes - Himanshu Mittal; Yih-Min Wu; Ting-Li Lin; Cédric P. Legendre; Sushil Gupta; Benjamin M. Yang (Acta Geophysica, 2019)

Transcription Factor 2I Regulates Neuronal Development via TRPC3 in 7q11.23 Disorder Models - Marielle H. S. Deurloo; Ekaterina Turlova; Wen-Liang Chen; You Wei Lin; Elaine Tam; Nardos G. Tassew; Michael Wu; Ya-Chi Huang; Jacqueline N. Crawley; Philippe P. Monnier; Alexander J. A. Groffen; Hong-Shuo Sun; et al. (Molecular Neurobiology, 2019)

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Identify a shared neural circuit linking multiple neuropsychiatric symptoms with Alzheimer’s pathology - Xixi Wang; Ping Ren; Mark Mapstone; Yeates Conwell; Anton P. Porsteinsson; John J. Foxe; Rajeev D. S. Raizada; Feng Lin (Brain Imaging and Behavior, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

A geometric morphometric relationship predicts stone flake shape and size variability - Will Archer; Cornel M. Pop; Zeljko Rezek; Stefan Schlager; Sam C. Lin; Marcel Weiss; Tamara Dogandžić; Dawit Desta; Shannon P. McPherron (Archaeological and Anthropological Sciences, 2018)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

A Comparative Placebo-Controlled Clinical Trial of the Efficacy and Safety of Interferon β-1a Formulations for S.C. Administration in Patients with Remitting Multiple Sclerosis: First-Year Results - A. N. Boiko; L. P. Bosenko; V. V. Vasilovskii; L. I. Volkova; M. N. Zakharova; S. V. Kotov; E. V. Lekomtseva; T. I. Negrich; E. V. Parshina; O. P. Patrusheva; S. V. Prokopenko; D. V. Sazonov; et al. (Neuroscience and Behavioral Physiology, 2018)

Enhancement of photocatalytic activity of titanium dioxide using non-metal doping methods under visible light: a review - M. Nasirian; Y. P. Lin; C. F. Bustillo-Lecompte; M. Mehrvar (International Journal of Environmental Science and Technology, 2018)

Pharmacodynamic and Pharmacokinetic Properties of AFPep, a Novel Peptide for the Treatment of Breast Cancer - J. A. Bennett; W. Mansouri; Q. Lin; P. Feustel; T. T. Andersen (International Journal of Peptide Research and Therapeutics, 2018)

Spatiotemporal variations of annual shallow soil temperature on the Tibetan Plateau during 1983–2013 - Fuxin Zhu; Lan Cuo; Yongxin Zhang; Jing-Jia Luo; Dennis P. Lettenmaier; Yumei Lin; Zhe Liu (Climate Dynamics, 2018)

Groundwater sustainability and groundwater/surface-water interaction in arid Dunhuang Basin, northwest China - Jingjing Lin; Rui Ma; Yalu Hu; Ziyong Sun; Yanxin Wang; Colin P. R. McCarter (Hydrogeology Journal, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Correction to: Predictive Simulations of Neuromuscular Coordination and Joint-Contact Loading in Human Gait - Yi-Chung Lin; Jonathan P. Walter; Marcus G. Pandy (Annals of Biomedical Engineering, 2018)

Predictive Simulations of Neuromuscular Coordination and Joint-Contact Loading in Human Gait - Yi-Chung Lin; Jonathan P. Walter; Marcus G. Pandy (Annals of Biomedical Engineering, 2018)

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Burly1 is a mouse QTL for lean body mass that maps to a 0.8-Mb region of chromosome 2 - Cailu Lin; Brad D. Fesi; Michael Marquis; Natalia P. Bosak; Anna Lysenko; Mohammed Amin Koshnevisan; Fujiko F. Duke; Maria L. Theodorides; Theodore M. Nelson; Amanda H. McDaniel; Mauricio Avigdor; Charles J. Arayata; et al. (Mammalian Genome, 2018)

Synthesis of nucleobase-neomycin conjugates and evaluation of their DNA binding, cytotoxicities, and antibacterial properties - Siwen Wang; Mandeep Singh; Mingheng Ling; Danni Li; Krege M. Christison; Joan Lin-Cereghino; Geoff P. Lin-Cereghino; Liang Xue (Medicinal Chemistry Research, 2018)

Combination Therapy with Low-Dose IVIG and a C1-esterase Inhibitor Ameliorates Brain Damage and Functional Deficits in Experimental Ischemic Stroke - Xinzhi Chen; Thiruma V. Arumugam; Yi-Lin Cheng; Jong-Hwan Lee; Srinivasulu Chigurupati; Mark P. Mattson; Milan Basta (NeuroMolecular Medicine, 2018)

Delivery of adjuvant chemotherapy among stage III colon cancer patients at a public versus private hospital in New York City - Daniel Lin; Judith D. Goldberg; Tsivia Hochman; Benjamin A. Levinson; Maria Khan; Elliot Newman; Lawrence P. Leichman; Heather T. Gold (Cancer Causes & Control, 2018)

Formation of chlorite rims and the impact of pore-lining chlorite on reservoir quality: a case study from Shiqianfeng sandstones in upper Permian of Dongpu Depression, Bohai Bay Basin, eastern China - P. J. Ma; C. Y. Lin; S. Q. Zhang; C. M. Dong; Y. F. Xu (Australian Journal of Earth Sciences, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Spatiotemporal patterns of annual and seasonal precipitation extreme distributions across China and potential impact of tropical cyclones - Xihui Gu; Qiang Zhang; Vijay P. Singh; Lin Liu; Peijun Shi (International Journal of Climatology, 2017)
Statistical properties of annual and seasonal daily maximum precipitation in terms of nonstationarity, upper tail properties, and impact of tropical cyclones ( TCs ) were analysed, using data from 728 meteorological stations across China and TCs tracks data covering a period of 1951–2014. The change points and trends detected by stepwise regression method and modified Mann–Kendall, respectively, provide limited evidence of the violation of the stationarity assumption in both annual and seasonal extreme precipitation, and we cannot make conclusive statements about the presence of a possible climate change signal. For stationary stations, the ratio of scale to location parameters of generalized extreme value ( GEV ) distribution shows exponential for annual and seasonal extreme precipitation in some sub‐regions. On the other hand, annual and seasonal maxima point to an unbounded‐above and heavy‐tail behaviour, and discussion of these upper tail properties in light of mixtures of different rainfall‐generating mechanisms is provided. In addition, anomalous values of the GEV shape parameter are associated with TCs in controlling the upper tail of annual maxima on China's coastal areas with strong spatial heterogeneities.

Controlled Release of Vanadium from a Composite Scaffold Stimulates Mesenchymal Stem Cell Osteochondrogenesis - S. D. Schussler; K. Uske; P. Marwah; F. W. Kemp; J. D. Bogden; S. S. Lin; Treena Livingston Arinzeh (The AAPS Journal, 2017)

Cardiotoxicity Associated with Nicotinamide Phosphoribosyltransferase Inhibitors in Rodents and in Rat and Human-Derived Cells Lines - D. L. Misner; M. A. Kauss; J. Singh; H. Uppal; A. Bruening-Wright; B. M. Liederer; T. Lin; B. McCray; N. La; T. Nguyen; D. Sampath; P. S. Dragovich; et al. (Cardiovascular Toxicology, 2017)

Tissue and cell-type co-expression networks of transcription factors and wood component genes in Populus trichocarpa - Rui Shi; Jack P. Wang; Ying-Chung Lin; Quanzi Li; Ying-Hsuan Sun; Hao Chen; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2017)

CRISPR-Cas9 and CRISPR-Cpf1 mediated targeting of a stomatal developmental gene EPFL9 in rice - Xiaojia Yin; Akshaya K. Biswal; Jacqueline Dionora; Kristel M. Perdigon; Christian P. Balahadia; Shamik Mazumdar; Caspar Chater; Hsiang-Chun Lin; Robert A. Coe; Tobias Kretzschmar; Julie E. Gray; Paul W. Quick; et al. (Plant Cell Reports, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Increased risk of chronic osteomyelitis after hip replacement: a retrospective population-based cohort study in an Asian population - D.-Z. Hung; N. Tien; C.-L. Lin; Y.-R. Lee; C. C. N. Wang; J.-J. Chen; Y.-P. Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Soil priming effects following substrates addition to biochar-treated soils after 431 days of pre-incubation - Yu Luo; Qimei Lin; M. Durenkamp; A. J. Dungait; P. C. Brookes (Biology and Fertility of Soils, 2017)

Heat budget of the western Pacific warm pool and the contribution of eddy heat transport diagnosed from HYCOM assimilation - J. Chi; P. Shi; W. Zhuang; X. Lin; X. Cheng; Yan Du (Journal of Oceanography, 2017)

Conformational changes during human P2X7 receptor activation examined by structural modelling and cysteine-based cross-linking studies - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2017)

Effects of Collagen Crosslink Augmentation on Mechanism of Compressive Load Sharing in Intervertebral Discs - Thomas P. Hedman; Weng-Pin Chen; Leou-Chyr Lin; Hsiu-Jen Lin; Shih-Youeng Chuang (Journal of Medical and Biological Engineering, 2017)
Exogenous crosslinking has been shown to have potential for treating disc degeneration and back pain due to its ability to increase the strength and toughness of the annulus fibrosus, increase intervertebral joint stability, decrease intradiscal pressure, and increase fluid flow through the disc. Some results imply that crosslink augmentation may also lead to changes in the compressive load sharing properties of the disc. The objective of the present study was to evaluate directional stress distribution changes of the disc following genipin crosslinking treatment. Bovine lumbar motion segments were randomly divided into control and crosslinked groups. Annular strains were determined from simultaneous deformation measurements at various time points during compressive creep testing. Four stress components of the annulus were then calculated according to the previously measured modulus data. Immediately after the application of a 750-N compressive load, mean axial and radial compressive stresses in the crosslinked group were twofold higher than control means. Conversely, mean lamellae-aligned and circumferential tensile stresses of the crosslinked discs were 8- and threefold lower, respectively, compared to control means. After 1-h creep loading, the two compressive mean stresses in both the control and genipin-crosslinked specimens increased approximately threefold from their initial 750-N-loaded values. The two tensile mean stresses in the crosslinked group remained lower than the respective levels of the control means after creep loading. A greater proportion of annular compressive load support under compressive creep loading, with a commensurate decrease in both tensile stresses and strains, was seen in the discs following exogenous crosslink augmentation.

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

Transcriptomic imprints of adaptation to fresh water: parallel evolution of osmoregulatory gene expression in the Alewife - Jonathan P. Velotta; Jill L. Wegrzyn; Samuel Ginzburg; Lin Kang; Sergiusz Czesny; Rachel J. O'Neill; Stephen D. McCormick; Pawel Michalak; Eric T. Schultz (Molecular Ecology, 2017)
Comparative approaches in physiological genomics offer an opportunity to understand the functional importance of genes involved in niche exploitation. We used populations of Alewife ( Alosa pseudoharengus ) to explore the transcriptional mechanisms that underlie adaptation to fresh water. Ancestrally anadromous Alewives have recently formed multiple, independently derived, landlocked populations, which exhibit reduced tolerance of saltwater and enhanced tolerance of fresh water. Using RNA ‐seq, we compared transcriptional responses of an anadromous Alewife population to two landlocked populations after acclimation to fresh (0 ppt) and saltwater (35 ppt). Our results suggest that the gill transcriptome has evolved in primarily discordant ways between independent landlocked populations and their anadromous ancestor. By contrast, evolved shifts in the transcription of a small suite of well‐characterized osmoregulatory genes exhibited a strong degree of parallelism. In particular, transcription of genes that regulate gill ion exchange has diverged in accordance with functional predictions: freshwater ion‐uptake genes (most notably, the ‘freshwater paralog’ of Na + /K + ‐ ATP ase α‐subunit) were more highly expressed in landlocked forms, whereas genes that regulate saltwater ion secretion (e.g. the ‘saltwater paralog’ of NKA α) exhibited a blunted response to saltwater. Parallel divergence of ion transport gene expression is associated with shifts in salinity tolerance limits among landlocked forms, suggesting that changes to the gill's transcriptional response to salinity facilitate freshwater adaptation.

Regulation of fibronectin gene expression in cardiac fibroblasts by scleraxis - Rushita A. Bagchi; Justin Lin; Ryan Wang; Michael P. Czubryt (Cell and Tissue Research, 2016)

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; James P. Keener; Robert Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2016)

Effects of probiotics on soil microbial activity, biomass and enzymatic activity under cover crops in field and greenhouse studies - Ahsan M. Rajper; Ranjith P. Udawatta; Robert J. Kremer; Chung-ho Lin; Shibu Jose (Agroforestry Systems, 2016)

The agranular and granular insula differentially contribute to gambling-like behavior on a rat slot machine task: effects of inactivation and local infusion of a dopamine D4 agonist on reward expectancy - P. J. Cocker; M. Y. Lin; M. M. Barrus; B. Le Foll; C. A. Winstanley (Psychopharmacology, 2016)

Mapping anhedonia-specific dysfunction in a transdiagnostic approach: an ALE meta-analysis - Bei Zhang; Pan Lin; Huqing Shi; Dost Öngür; Randy P. Auerbach; Xiaosheng Wang; Shuqiao Yao; Xiang Wang (Brain Imaging and Behavior, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Spatiotemporal properties of growing season indices during 1961–2010 and possible association with agroclimatological regionalization of dominant crops in Xinjiang, China - Hui Ci; Qiang Zhang; Vijay P. Singh; Mingzhong Xiao; Lin Liu (Meteorology and Atmospheric Physics, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Early detection of Mycobacterium tuberculosis complex in BACTEC MGIT cultures using nucleic acid amplification - S. Y. Lin; S. C. Hwang; Y. C. Yang; C. F. Wang; Y. H. Chen; T. C. Chen; P. L. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Peptide Regulation of Skin Fibroblast Functions during Their Aging In Vitro - N. S. Lin’kova; A. O. Drobintseva; O. A. Orlova; E. P. Kuznetsova; V. O. Polyakova; I. M. Kvetnoy; V. Kh. Khavinson (Bulletin of Experimental Biology and Medicine, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Entropy‐based spatiotemporal patterns of precipitation regimes in the Huai River basin, China - Qiang Zhang; Yongjie Zheng; Vijay P. Singh; Mingzhong Xiao; Lin Liu (International Journal of Climatology, 2016)
Spatiotemporal patterns of precipitation regimes in terms of precipitation amount and number of precipitation days at different time scales are investigated using the entropy‐based methodologies in the Huai River basin, China. Trends of precipitation variability are quantitatively evaluated using the modified Mann–Kendall trend test method. Correlations between the largest 7‐day precipitation amount (R × 7day) and precipitation variability within 1 year are also analysed. Results indicate the following: (1) there is increasing nonuniformity of annual precipitation amount and annual precipitation days from south to north in the Huai River basin, indicating larger precipitation variability in the northern parts. Transition of precipitation changes is evident in the basin which is reflected by decreasing precipitation variability in the north and increasing precipitation variability in the south. (2) The disorder indices (DIs) exhibit variations at different time scales. In general, precipitation variability is larger at shorter time scales, such as daily, and is smaller at longer time scales, such as annual. (3) Significant relations are identified between the DI and extreme precipitation events, i.e. significant relations between apportionment DI and the largest 7‐day precipitation amount and it is particularly the case in the central and southwestern parts. Thus, it can be said that higher precipitation variability is due to higher frequency of extreme precipitation regimes. Results of this study are of practical significance for planning and management of water resources and agricultural irrigation and agricultural activities during climate change and particularly for enhancement of measures for mitigation of consequences of climate change.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Defining the structural characteristics of annexin V binding to a mimetic apoptotic membrane - Jingxiong Lu; Anton P. Le Brun; Seong Hoong Chow; Takuya Shiota; Bo Wang; Tsung-Wu Lin; Guei-Sheung Liu; Hsin-Hui Shen (European Biophysics Journal, 2015)

Prior human polyomavirus and papillomavirus infection and incident lung cancer: a nested case–control study - Danny V. Colombara; Lisa E. Manhart; Joseph J. Carter; Stephen E. Hawes; Noel S. Weiss; James P. Hughes; Matt J. Barnett; Gary E. Goodman; Jennifer S. Smith; You-Lin Qiao; Denise A. Galloway (Cancer Causes & Control, 2015)

Extracellular sodium and potassium levels modulate cardiac conduction in mice heterozygous null for the Connexin43 gene - Sharon A. George; Katherine J. Sciuto; Joyce Lin; Mohamed E. Salama; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Influence of Regional Difference in Bone Mineral Density on Hip Fracture Site in Elderly Females by Finite Element Analysis - Z. L. Lin; P. F. Li; Z. H. Pang; X. H. Zheng; F. Huang; H. H. Xu; Q. L. Li (Cell Biochemistry and Biophysics, 2015)

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; Gregory S. Hoeker; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Two New Species of the Genus Criotettix Bolivar (Orthoptera: Tetrigidae), with a Key to the Species of the Genus from China - W A Deng; Z M Zheng; S Z Wei; M P Lin; L L Lin (Neotropical Entomology, 2015)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Identification and characterization of a late gene encoded by grouper iridovirus 2L (GIV‐2L) - H‐Y Lin; C‐F Cheng; P P Chiou; C‐J Liou; J‐C Yiu; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) belongs to the Ranavirus genus and is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. In this study, we identified and characterized the GIV‐2L gene, which encodes a protein of unknown function. GIV‐2L is 1242 bp in length, with a predicted protein mass of 46.2 kDa. It displayed significant identity only with members of the Ranavirus and Iridovirus genera. We produced mouse monoclonal antibodies against the GIV‐2L protein by immunizing mice with GIV‐2L‐His‐tag recombinant protein. By inhibiting de novo protein and DNA synthesis in GIV‐infected cells, we showed that GIV‐2L was a late gene during the viral replication. Finally, immunofluorescence microscopy revealed that GIV‐2L protein accumulated in both the nucleus and cytoplasm of infected cells. These results offer important insights into the pathogenesis of GIV.

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Ambient air concentrations of PCDD/Fs, coplanar PCBs, PBDD/Fs, and PBDEs and their impacts on vegetation and soil - Y.-C. Kuo; Y.-C. Chen; M.-Y. Lin; L.-H. Young; H.-T. Hsu; S.-H. Liou; T.-N. Wu; L.-C. Wang; P.-J. Tsai (International Journal of Environmental Science and Technology, 2015)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

The application of the cluster identification method for the detection of leakages in water distribution networks - H.-Y. Lin; B.-W. Lin; P.-H. Li; J.-J. Kao (International Journal of Environmental Science and Technology, 2015)

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

Pharmacokinetics and pharmacodynamics of 3,3′-diindolylmethane (DIM) in regulating gene expression of phase II drug metabolizing enzymes - Tien-Yuan Wu; Ying Huang; Chengyue Zhang; Zheng-Yuan Su; Sarandeep Boyanapalli; Tin Oo Khor; Hu Wang; Hongxia Lin; Murugesan Gounder; Leonid Kagan; Ioannis P. Androulakis; Ah-Ng Tony Kong (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Enemies lost: parallel evolution in structural defense and tolerance to herbivory of invasive Jacobaea vulgaris - Tiantian Lin; Leonie Doorduin; Andries Temme; Thijs L. Pons; Gerda E. M. Lamers; Niels P. R. Anten; Klaas Vrieling (Biological Invasions, 2015)

Infections of nervous necrosis virus in wild and cage‐reared marine fish from S outh C hina S ea with unexpected wide host ranges - X D Liu; J N Huang; S P Weng; X Q Hu; W J Chen; Z D Qin; X X Dong; X L Liu; Y Zhou; M Asim; W M Wang; J G He; et al. (Journal of Fish Diseases, 2015)
The concerns about the impact of the nervous necrosis virus ( NNV ) infections in wild fish have been raised. This paper presents the results of quarterly surveys of NNV in wild and cage‐reared marine fish from South China Sea. Samples of 892 wild fish belonging to 69 species and 381 cage‐reared fish belonging to 11 species were collected and were detected by seminested PCR and nested PCR . In the case of seminested PCR , the positive signal was detected in 3.0% and 3.1% samples of wild and cage‐reared fish, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 42.3% and 63.0% samples of wild and cage‐reared fish, respectively. If the fish species were considered, the positive signal was detected in 21.7% and 72.7% species of wild and cage‐reared fish by seminested PCR assay, respectively. However, by nested RT ‐ PCR , the positive signal was observed in 65.2% and 100% species of wild and cage‐reared fish, respectively. The nucleotide sequences of the nested PCR products were determined. Phylogenetic tree showed that all the obtained viral isolates belonged to the red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype. Thirty‐five species of the marine fish were the new hosts of NNV .

Peptide Regulation of Cells Renewal Processes in Kidney Tissue Cultures from Young and Old Animals - N. I. Chalisova; N. S. Lin’kova; T. E. Nichik; A. P. Ryzhak; A. V. Dudkov; G. A. Ryzhak (Bulletin of Experimental Biology and Medicine, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Quantitative Prediction of Human Pharmacokinetics for mAbs Exhibiting Target-Mediated Disposition - Aman P. Singh; Wojciech Krzyzanski; Steven W. Martin; Gregory Weber; Alison Betts; Alaa Ahmad; Anson Abraham; Anup Zutshi; John Lin; Pratap Singh (The AAPS Journal, 2015)

Anti-tuberculosis treatments and risk of hepatocellular carcinoma in tuberculosis patients with liver cirrhosis: a population-based case–control study - Y.-P. Lim; C.-L. Lin; D.-Z. Hung; Y.-N. Lin; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Rhizobium capsici sp. nov., isolated from root tumor of a green bell pepper (Capsicum annuum var. grossum) plant - Shih-Yao Lin; Mei-Hua Hung; Asif Hameed; You-Cheng Liu; Yi-Han Hsu; Cheng-Zhe Wen; A. B. Arun; Hans-Jürgen Busse; Stefanie P. Glaeser; Peter Kämpfer; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Removal of antineoplastic drugs cyclophosphamide, ifosfamide, and 5-fluorouracil and a vasodilator drug pentoxifylline from wastewaters by ozonation - Angela Yu-Chen Lin; Julia Han-Fang Hsueh; P. K. Andy Hong (Environmental Science and Pollution Research, 2015)

Description of a New Species of the Genus Macromotettixoides Zheng (Orthoptera: Tetrigoidea: Metrodorinae) from China - W A Deng; C-L Lei; Z M Zheng; X D Li; L L Lin; M P Lin (Neotropical Entomology, 2014)

Evaluating the Anticancer Properties of Liposomal Copper in a Nude Xenograft Mouse Model of Human Prostate Cancer: Formulation, In Vitro, In Vivo, Histology and Tissue Distribution Studies - Yan Wang; San Zeng; Tien-Min Lin; Lisa Krugner-Higby; Doug Lyman; Dana Steffen; May P. Xiong (Pharmaceutical Research, 2014)

Trends in the susceptibility of commonly encountered clinically significant anaerobes and susceptibilities of blood isolates of anaerobes to 16 antimicrobial agents, including fidaxomicin and rifaximin, 2008–2012, northern Taiwan - F. D. Wang; C. H. Liao; Y. T. Lin; W. H. Sheng; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Vertical distributions of bound saturated fatty acids and compound-specific stable carbon isotope compositions in sediments of two lakes in China: implication for the influence of eutrophication - Lifang Wang; Yongqiang Xiong; Fengchang Wu; Qiuhua Li; Tian Lin; John P. Giesy (Environmental Science and Pollution Research, 2014)

Association between herpes zoster and end stage renal disease entrance in chronic kidney disease patients: a population-based cohort study - S.-Y. Lin; J.-H. Liu; H.-C. Yeh; C.-L. Lin; I.-J. Tsai; P.-C. Chen; F.-C. Sung; Y.-F. Yang; C.-C. Huang; D. E. Morisky; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Seasonal dynamics of physical and biological processes in the central California Current System: A modeling study - Lin Guo; Fei Chai; Peng Xiu; Huijie Xue; Shivanesh Rao; Yuguang Liu; Francisco P. Chavez (Ocean Dynamics, 2014)

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Two New Species of the Genus Xistra Bolivar (Orthoptera: Tetrigidae) from China - X D Li; W A Deng; Z M Zheng; M P Lin; C W Lu (Neotropical Entomology, 2014)

Effects of Dietary Selenium Deficiency on mRNA Levels of Twenty-One Selenoprotein Genes in the Liver of Layer Chicken - C. P. Liu; J. Fu; S. L. Lin; X. S. Wang; S. Li (Biological Trace Element Research, 2014)

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Detection of human JCPyV and BKPyV in diffuse large B-cell lymphoma of the GI tract - C. E. Tseng; C. M. Yeh; C. Y. Fang; J. Shay; P. L. Chen; M. C. Lin; D. Chang; M. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A novel rhizobacterium Bk7 for biological control of brown sheath rot of rice caused by Pseudomonas fuscovaginae and its mode of action - Kaleem Ullah Kakar; Y.-P. Duan; Zarqa Nawaz; Guochang Sun; Abdlwareth A. Almoneafy; M. Auwal Hassan; Ahmed Elshakh; Bin Li; Guan-Lin Xie (European Journal of Plant Pathology, 2014)

Blockade of the renin–angiotensin system inhibits growth of colorectal cancer liver metastases in the regenerating liver - Shir Lin Koh; E. I. Ager; P. L. N. Costa; C. Malcontenti-Wilson; V. Muralidharan; C. Christophi (Clinical & Experimental Metastasis, 2014)

BDNF and Exercise Enhance Neuronal DNA Repair by Stimulating CREB-Mediated Production of Apurinic/Apyrimidinic Endonuclease 1 - Jenq-Lin Yang; Yu-Ting Lin; Pei-Chin Chuang; Vilhelm A. Bohr; Mark P. Mattson (NeuroMolecular Medicine, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Evaluating the protective efficacy of antigen combinations against P hotobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L. - L‐P Ho; C‐J Chang; H‐C Liu; H‐L Yang; J H‐Y Lin (Journal of Fish Diseases, 2014)
Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen P hotobacterium damselae ssp. piscicida , and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P . damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 ( rHSP 60), recombinant α‐enolase ( rENOLASE ) and recombinant glyceraldehyde‐3‐phosphate dehydrogenase ( rGAPDH ), we analysed the doses that elicited the best immune responses and found that this occurred at a total of 30 μg of antigen per fish. Subsequently, vaccination of fish with rHSP 60, rENOLASE and rGAPDH achieved 46.9, 52 and 25% relative per cent survival (RPS), respectively. In addition, bivalent subunit vaccines – combination I ( rHSP 60 + rENOLASE ), combination II ( rENOLASE + rGAPDH ) and combination III ( rHSP 60 + rGAPDH ) – were administered and the RPS in these groups (65.6, 64.0 and 48.4%, respectively), was higher than that achieved with single‐antigen administration. Finally, in combination IV , the trivalent vaccine rHSP 60 + rENOLASE + rGAPDH , the RPS was 1.6%. Taken together, our results suggest that combinations of two antigens may achieve a better efficiency than monovalent or trivalent antigens, and this may provide new insights into pathogen prevention strategies.

Recommendations for the processing and storage of water samples before polymerase chain reaction (PCR) analysis - BJ Gilpin; M Devane; F Nourozi; B Robson; P Scholes; S Lin (New Zealand Journal of Marine and Freshwater Research, 2013)
A range of options for the storage and partial processing of water samples before polymerase chain reaction (PCR) analysis were evaluated. In addition, temporal storage of extracted DNA at 4 °C was investigated. Filtering the water sample and then storing that filter at −20 °C for up to six months before DNA extraction was equivalent to extracting DNA immediately. Freezing a water sample resulted in an immediate 1 log loss of PCR signal, although thereafter the sample was stable for at least three months. A rapid loss of detectable PCR product was found when storing a water sample at 4 °C for longer than one week. Extracted DNA could be stored at 4 °C for at least six months without considerable loss of PCR signal.

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

Twentieth century human and climate impacts on a large mountain lake in southwest China - Xinchun Guo; Aaron P. Potito; Lin Luo; David W. Beilman (Hydrobiologia, 2013)

Mutant strains of Pichia pastoris with enhanced secretion of recombinant proteins - Sasha Larsen; Jun Weaver; Katherine de Sa Campos; Rhobe Bulahan; Jackson Nguyen; Heather Grove; Amy Huang; Lauren Low; Namphuong Tran; Seth Gomez; Jennifer Yau; Thomas Ilustrisimo; et al. (Biotechnology Letters, 2013)

Volatile halocarbon emissions by three tropical brown seaweeds under different irradiances - Fiona Seh-Lin Keng; Siew-Moi Phang; Noorsaadah Abd Rahman; Emma C. Leedham; Claire Hughes; Andrew D. Robinson; Neil R. P. Harris; John A. Pyle; William T. Sturges (Journal of Applied Phycology, 2013)

Quantitative and qualitative characteristics of dissolved organic matter from eight dominant aquatic macrophytes in Lake Dianchi, China - Xiaoxia Qu; Li Xie; Ying Lin; Yingchen Bai; Yuanrong Zhu; Fazhi Xie; John P. Giesy; Fengchang Wu (Environmental Science and Pollution Research, 2013)

In situ activity of a dominant P rochlorococcus ecotype ( eHL ‐ II ) from rRNA content and cell size - Yajuan Lin; Katrina Gazsi; Veronica P. Lance; Alyse A. Larkin; Jeremy W. Chandler; Erik R. Zinser; Zackary I. Johnson (Environmental Microbiology, 2013)
Summary In the open ocean genetically diverse clades of the unicellular cyanobacteria P rochlorococcus are biogeographically structured along environmental gradients, yet little is known about their in situ activity. To address this gap, here we use the numerically dominant P rochlorococcus clade e HL ‐ II (e MIT 9312) as a model organism to develop and apply a method to examine their in situ activity using r RNA content and cell size as metrics of cellular physiology. For two representative isolates ( MIT 9312 and MIT 9215) r RNA cell −1 increases linearly with specific growth rate but is anticorrelated with cell size indicated by flow cytometrically measured ( SSC ). Although each strain has a unique relationship between cellular r RNA (or cell size) and growth rate, both strains have the same strong positive correlation between r RNA cell −1 SSC −1 and growth rate. We field test this approach and observe distinct patterns of eHL ‐ II clade specific activity (r RNA cell −1 SSC −1 ) with depth that are consistent with patterns of photosynthetic rates. This molecular technique provides unique insight into the ecology of P rochlorococcus and could potentially be expanded to include other microbes to unravel the ecological and biogeochemical contributions of genetically distinct marine side scatter microbes.

Temporal and spectral characterization of the photosynthetic reaction center from Heliobacterium modesticaldum - Adrien Chauvet; Josephine Sarrou; Su Lin; Steven P. Romberger; John H. Golbeck; Sergei Savikhin; Kevin E. Redding (Photosynthesis Research, 2013)

Core–shell magnetite-silica dithiocarbamate-derivatised particles achieve the Water Framework Directive quality criteria for mercury in surface waters - C. B. Lopes; P. Figueira; D. S. Tavares; Z. Lin; A. L. Daniel-da-Silva; A. C. Duarte; J. Rocha; T. Trindade; E. Pereira (Environmental Science and Pollution Research, 2013)

Evaluation of MODIS surrogates for meteorological humidity data in east Africa - Shengpan Lin; Nathan J. Moore; Joseph P. Messina; Jiaping Wu (International Journal of Remote Sensing, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Rapid decrease in tumor perfusion following VEGF blockade predicts long-term tumor growth inhibition in preclinical tumor models - Alexandra Eichten; Alexander P. Adler; Blerta Cooper; Jennifer Griffith; Yi Wei; George D. Yancopoulos; Hsin Chieh Lin; Gavin Thurston (Angiogenesis, 2013)

Assessing whole-field sprinkler irrigation application uniformity - Lin Zhang; Gary P. Merkley; Kasem Pinthong (Irrigation Science, 2013)

An abrupt backreef infilling in a Holocene reef, Paraoir, Northwestern Luzon, Philippines - Shou-Yeh Gong; Tso-Ren Wu; Fernando P. Siringan; Ke Lin; Chuan-Chou Shen (Coral Reefs, 2013)

Neuroanatomical consequences of very preterm birth in middle childhood - Ilyse D. Lax; Emma G. Duerden; Sarah Y. Lin; M. Mallar Chakravarty; Elizabeth J. Donner; Jason P. Lerch; Margot J. Taylor (Brain Structure and Function, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

Water quality associated public health risk in Bo, Sierra Leone - David H. Jimmy; Abu J. Sundufu; Anthony P. Malanoski; Kathryn H. Jacobsen; Rashid Ansumana; Tomasz A. Leski; Umaru Bangura; Alfred S. Bockarie; Edries Tejan; Baochuan Lin; David A. Stenger (Environmental Monitoring and Assessment, 2013)

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Human Health Risk Assessment of 16 Priority Polycyclic Aromatic Hydrocarbons in Soils of Chattanooga, Tennessee, USA - Erika Hussar; Sean Richards; Zhi-Qing Lin; Robert P. Dixon; Kevin A. Johnson (Water, Air, & Soil Pollution, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Effects of the fungicide metiram in outdoor freshwater microcosms: responses of invertebrates, primary producers and microbes - Ronghua Lin; Laura Buijse; Mauricio R. Dimitrov; Peter Dohmen; Sujitra Kosol; Lorraine Maltby; Ivo Roessink; Jos A. Sinkeldam; Hauke Smidt; René P. A. Van Wijngaarden; Theo C. M. Brock (Ecotoxicology, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Deletion of Siah-interacting protein gene in Drosophila causes cardiomyopathy - Michelle E. Casad; Lin Yu; Joseph P. Daniels; Matthew J. Wolf; Howard A. Rockman (Molecular Genetics and Genomics, 2012)

Relationships between common irrigation application uniformity indicators - Lin Zhang; Gary P. Merkley (Irrigation Science, 2012)

Linking Carbon Saturation Concepts to Nitrogen Saturation and Retention - Michael J. Castellano; Jason P. Kaye; Henry Lin; John P. Schmidt (Ecosystems, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

First Isolation of Candida dubliniensis from Oral Cavities of Dermatological Patients in Nanjing, China - Yi P. Ge; Guo X. He; Tong Lin; Gui X. Lu; Yong N. Shen; Wei D. Liu (Mycopathologia, 2011)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Norflurazon and Simazine Removal from Surface Water Using a Constructed Wetland - P. Chris Wilson; Hai Lu; Youjian Lin (Bulletin of Environmental Contamination and Toxicology, 2011)

A Bayesian population analysis of the development of type 2 diabetes in the offspring of diabetic parents - C. W. Lin; J. H. Warram; P. Veng-Pedersen (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Optical coherence tomography: fundamental principles, instrumental designs and biomedical applications - Dan P. Popescu; Lin-P’ing Choo-Smith; Costel Flueraru; Youxin Mao; Shoude Chang; John Disano; Sherif Sherif; Michael G. Sowa (Biophysical Reviews, 2011)

A nested case–control study of low birthweight among cosmetologists - Michele L. Herdt-Losavio; Shao Lin; Charlotte M. Druschel; Syni-An Hwang; Matthew P. Mauer; G. Anders Carlson (International Archives of Occupational and Environmental Health, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

The controlled in vitro susceptibility of gastrointestinal pathogens to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Papillary thyroid cancer incidence rates vary significantly by birthplace in Asian American women - Pamela L. Horn-Ross; Laura A. McClure; Ellen T. Chang; Christina A. Clarke; Theresa H. M. Keegan; Rudolph P. Rull; Thu Quach; Scarlett Lin Gomez (Cancer Causes & Control, 2011)

Evaluation of potential integration of entrapped mixed microbial cell and membrane bioreactor processes for biological wastewater treatment/reuse - Jia Zhu; C. F. Lin; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2011)

Suprachoroidal Drug Delivery to the Back of the Eye Using Hollow Microneedles - Samirkumar R. Patel; Angela S. P. Lin; Henry F. Edelhauser; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Adaptation or preadaptation: why are keelback snakes (Tropidonophis mairii) less vulnerable to invasive cane toads (Bufo marinus) than are other Australian snakes? - John Llewelyn; Ben L. Phillips; Greg P. Brown; Lin Schwarzkopf; Ross A. Alford; Richard Shine (Evolutionary Ecology, 2011)

Typhoon Disturbance and Forest Dynamics: Lessons from a Northwest Pacific Subtropical Forest - Teng-Chiu Lin; Steven P. Hamburg; Kuo-Chuan Lin; Lih-Jih Wang; Chung-Te Chang; Yue-Joe Hsia; Matthew A. Vadeboncoeur; Cathy M. Mabry McMullen; Chiung-Pin Liu (Ecosystems, 2011)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Development of EST-PCR markers for Thinopyrum intermedium chromosome 2Ai#2 and their application in characterization of novel wheat-grass recombinants - M. J. Wang; Y. Zhang; Z. S. Lin; X. G. Ye; Y. P. Yuan; W. Ma; Z. Y. Xin (Theoretical and Applied Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Hydrological and biogeochemical controls on the timing and magnitude of nitrous oxide flux across an agricultural landscape - MICHAEL J. CASTELLANO; JOHN P. SCHMIDT; JASON P. KAYE; CHARLES WALKER; CHRIS B. GRAHAM; HENRY LIN; CURTIS J. DELL (Global Change Biology, 2010)
Anticipated increases in precipitation intensity due to climate change may affect hydrological controls on soil N 2 O fluxes, resulting in a feedback between climate change and soil greenhouse gas emissions. We evaluated soil hydrologic controls on N 2 O emissions during experimental water table fluctuations in large, intact soil columns amended with 100 kg ha −1 KNO 3 ‐N. Soil columns were collected from three landscape positions that vary in hydrological and biogeochemical properties ( N = 12 columns). We flooded columns from bottom to surface to simulate water table fluctuations that are typical for this site, and expected to increase given future climate change scenarios. After the soil was saturated to the surface, we allowed the columns to drain freely while monitoring volumetric soil water content, matric potential and N 2 O emissions over 96 h. Across all landscape positions and replicate soil columns, there was a positive linear relationship between total soil N and the log of cumulative N 2 O emissions ( r 2 = 0.47; P = 0.013). Within individual soil columns, N 2 O flux was a Gaussian function of water‐filled pore space (WFPS) during drainage (mean r 2 = 0.90). However, instantaneous maximum N 2 O flux rates did not occur at a consistent WFPS, ranging from 63% to 98% WFPS across landscape positions and replicate soil columns. In contrast, instantaneous maximum N 2 O flux rates occurred within a narrow range (−1.88 to −4.48 kPa) of soil matric potential that approximated field capacity. The relatively consistent relationship between maximum N 2 O flux rates and matric potential indicates that water filled pore size is an important factor affecting soil N 2 O fluxes. These data demonstrate that matric potential is the strongest predictor of the timing of N 2 O fluxes across soils that differ in texture, structure and bulk density.

Cultivation‐independent characterization of ‘ Candidatus Magnetobacterium bavaricum’ via ultrastructural, geochemical, ecological and metagenomic methods - C. Jogler; M. Niebler; W. Lin; M. Kube; G. Wanner; S. Kolinko; P. Stief; A. J. Beck; D. de Beer; N. Petersen; Y. Pan; R. Amann; et al. (Environmental Microbiology, 2010)
Summary ‘ Candidatus Magnetobacterium bavaricum’ is unusual among magnetotactic bacteria (MTB) in terms of cell size (8–10 µm long, 1.5–2 µm in diameter), cell architecture, magnetotactic behaviour and its distinct phylogenetic position in the deep‐branching Nitrospira phylum. In the present study, improved magnetic enrichment techniques permitted high‐resolution scanning electron microscopy and energy dispersive X‐ray analysis, which revealed the intracellular organization of the magnetosome chains. Sulfur globule accumulation in the cytoplasm point towards a sulfur‐oxidizing metabolism of ‘ Candidatus M. bavaricum’. Detailed analysis of ‘ Candidatus M. bavaricum’ microhabitats revealed more complex distribution patterns than previously reported, with cells predominantly found in low oxygen concentration. No correlation to other geochemical parameters could be observed. In addition, the analysis of a metagenomic fosmid library revealed a 34 kb genomic fragment, which contains 33 genes, among them the complete rRNA gene operon of ‘ Candidatus M. bavaricum’ as well as a gene encoding a putative type IV RubisCO large subunit.

Using hyperspectral remote sensing to estimate chlorophyll‐ a and phycocyanin in a mesotrophic reservoir - Lin Li; Rebecca E. Sengpiel; Denise L. Pascual; Lenore P. Tedesco; Jeffrey S. Wilson; Emmanuel Soyeux (International Journal of Remote Sensing, 2010)

Quantification of model uncertainty in environmental modeling - Ming Ye; Philip D. Meyer; Yu-Feng Lin; Shlomo P. Neuman (Stochastic Environmental Research and Risk Assessment, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Clinical and microbiological characteristics of community-acquired thoracic empyema or complicated parapneumonic effusion caused by Klebsiella pneumoniae in Taiwan - Y.-T. Lin; T.-L. Chen; L. K. Siu; S.-F. Hsu; C.-P. Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Positive culture for Klebsiella pneumoniae in relevant sputum samples as a predictor of rapidly fatal outcome in septic patients at medical intensive care units - T.-Y. Chuang; C.-J. Lin; T.-C. Chou; H.-H. Huang; S.-W. Lee; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

WRN mutations in Werner syndrome patients: genomic rearrangements, unusual intronic mutations and ethnic-specific alterations - Katrin Friedrich; Lin Lee; Dru F. Leistritz; Gudrun Nürnberg; Bidisha Saha; Fuki M. Hisama; Daniel K. Eyman; Davor Lessel; Peter Nürnberg; Chumei Li; María J. Garcia-F-Villalta; Carolien M. Kets; et al. (Human Genetics, 2010)

Alternative splicing and genetic diversity of the white collar-1 (wc-1) gene in cereal Phaeosphaeria pathogens - Ericka Yen-Hsin Chiu; Ying-Hong Lin; Wei Wu; Qijian Song; Pi-Fang Linda Chang; Ling-Yan Gao; Chun-Chi Chou; Peter P. Ueng (European Journal of Plant Pathology, 2010)

Hypoxia increases Sca-1/CD44 co-expression in murine mesenchymal stem cells and enhances their adipogenic differentiation potential - M. G. Valorani; A. Germani; W. R. Otto; L. Harper; A. Biddle; C. P. Khoo; W. R. Lin; M. I. Hawa; P. Tropel; M. P. Patrizi; P. Pozzilli; M. R. Alison (Cell and Tissue Research, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Veterinary antibiotic sorption to agroforestry buffer, grass buffer and cropland soils - Bei Chu; Keith W. Goyne; Stephen H. Anderson; Chung-Ho Lin; Ranjith P. Udawatta (Agroforestry Systems, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Rigorous pulse detection from full-waveform airborne laser scanning data - Yu-Ching Lin; J. P. Mills; S. Smith-Voysey (International Journal of Remote Sensing, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Organic-Solvent-Free Extraction Method for Determination of Carbamate and Carbamoyloxime Pesticides in Soil and Sediment Samples - Hai Lu; Youjian Lin; P. Chris Wilson (Bulletin of Environmental Contamination and Toxicology, 2009)

Identification of three immunodominant regions on leukotoxin protein of Fusobacterium necrophorum - D. B. Sun; R. Wu; G. L. Li; J. S. Zheng; X. P. Liu; Y. C. Lin; D. H. Guo (Veterinary Research Communications, 2009)

Intercomparison, interpretation, and assessment of spring phenology in North America estimated from remote sensing for 1982–2006 - MICHAEL A. WHITE; KIRSTEN M. De BEURS; KAMEL DIDAN; DAVID W. INOUYE; ANDREW D. RICHARDSON; OLAF P. JENSEN; JOHN O'KEEFE; GONG ZHANG; RAMAKRISHNA R. NEMANI; WILLEM J. D. Van LEEUWEN; JESSLYN F. BROWN; ALLARD De WIT; et al. (Global Change Biology, 2009)
Shifts in the timing of spring phenology are a central feature of global change research. Long‐term observations of plant phenology have been used to track vegetation responses to climate variability but are often limited to particular species and locations and may not represent synoptic patterns. Satellite remote sensing is instead used for continental to global monitoring. Although numerous methods exist to extract phenological timing, in particular start‐of‐spring (SOS), from time series of reflectance data, a comprehensive intercomparison and interpretation of SOS methods has not been conducted. Here, we assess 10 SOS methods for North America between 1982 and 2006. The techniques include consistent inputs from the 8 km Global Inventory Modeling and Mapping Studies Advanced Very High Resolution Radiometer NDVIg dataset, independent data for snow cover, soil thaw, lake ice dynamics, spring streamflow timing, over 16 000 individual measurements of ground‐based phenology, and two temperature‐driven models of spring phenology. Compared with an ensemble of the 10 SOS methods, we found that individual methods differed in average day‐of‐year estimates by ±60 days and in standard deviation by ±20 days. The ability of the satellite methods to retrieve SOS estimates was highest in northern latitudes and lowest in arid, tropical, and Mediterranean ecoregions. The ordinal rank of SOS methods varied geographically, as did the relationships between SOS estimates and the cryospheric/hydrologic metrics. Compared with ground observations, SOS estimates were more related to the first leaf and first flowers expanding phenological stages. We found no evidence for time trends in spring arrival from ground‐ or model‐based data; using an ensemble estimate from two methods that were more closely related to ground observations than other methods, SOS trends could be detected for only 12% of North America and were divided between trends towards both earlier and later spring.

A Two-Step Infinite α-Cuts Fuzzy Linear Programming Method in Determination of Optimal Allocation Strategies in Agricultural Irrigation Systems - H. W. Lu; G. H. Huang; Y. P. Lin; L. He (Water Resources Management, 2009)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The Impact of Iodine Excess on Thyroid Hormone Biosynthesis and Metabolism in Rats - K. Wang; Y. N. Sun; J. Y. Liu; L. Zhang; Y. Ye; L. X. Lin; Y. Q. Yan; Z. P. Chen (Biological Trace Element Research, 2009)

Colour variation is incongruent with mitochondrial lineages: cryptic speciation and subsequent diversification in a Gulf of California reef fish (Teleostei: Blennioidei) - H‐C. LIN; C. SÁNCHEZ‐ORTIZ; P. A. HASTINGS (Molecular Ecology, 2009)
The Gulf of California endemic reef fish, Acanthemblemaria crockeri (Blennioidei, Chaenopsidae), reportedly has two colour morphs, one with melanic lateral spots (‘Gulf’ morph) and one with orange spots (‘Cape’ morph). In this study, we recorded colour morph in both males and females and collected mitochondrial DNA sequence data for cytochrome c oxidase I (COI) and tRNA‐Pro/D‐loop of specimens from throughout the Gulf to explore the genetic basis of the colour morphs. Two highly divergent (HKY + I distance = 11.9% for COI), reciprocally monophyletic lineages were identified, consistent with the presence of two parapatric species. A 30‐km gap between the distributions of mitochondrial lineages roughly corresponds to a hypothesized former seaway across the Baja California peninsula north of La Paz, although the estimated divergence time (1.84 million years ago) is more recent than the hypothetical seaway (3–4 million years ago). Surprisingly, the distribution of mitochondrial species is not congruent with the distribution of either male or female colour morphs. Our analysis also revealed significant population differentiation within both species and no shared haplotypes among populations. The northern Gulf species includes four populations (NB, CB, NM and CM) corresponding to northern and central Baja and northern and central mainland sites, while the Cape species includes two populations (SB and SM) corresponding to the Baja and mainland sides of the southern Gulf. The NB/CB division corresponds to a hypothesized Plio–Pleistocene mid‐peninsular seaway. The level of genetic divergence documented in this lineage is extraordinary for a marine fish with a pelagic larval stage within a semi‐enclosed basin.

EMMC technology for treatment/reuse of dilute dairy wastewater - Rhoda Luo-Ting Lin; Joshua Lelemia Irvine; J. C. M. Kao; P. Y. Yang (Clean Technologies and Environmental Policy, 2009)

The in vitro susceptibility of Campylobacter spp. to the antibacterial effect of manuka honey - S. M. Lin; P. C. Molan; R. T. Cursons (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Raman spectroscopic study of K-lingunite at various pressures and temperatures - Lin-gun Liu; C.-C. Lin; Y. J. Yung; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Contrasting patterns of morphological and neutral genetic divergence among geographically proximate populations of sockeye salmon Oncorhynchus nerka in Lake Aleknagik, Alaska - J. Lin; E. Ziegler; T. P. Quinn; L. Hauser (Journal of Fish Biology, 2008)
Levels of differentiation in morphological traits (age at maturity, body length at age, egg mass and body depth) and spawning time were examined in sockeye salmon Oncorhynchus nerka from three geographically proximate but physically distinct creeks in Lake Aleknagik, Alaska. Happy Creek fish had significantly greater values for most measured morphological traits, and Eagle Creek fish spawned significantly later than fish in the other creeks. Phenotypic differentiation between creeks, measured as P ST , was then compared with microsatellite marker differentiation between creeks, measured as F ST . No correlations were apparent between P ST and F ST values, and P ST values were generally significantly larger than zero ( P ST = 0·0018–0·31) whereas F ST values were not ( F ST =−0·0004 to 0·0016). The insignificant pair‐wise F ST values between creek samples indicated that gene flow occurs between creeks, assuming the creek populations have reached migration–drift equilibrium. However, the strong homing behaviour of sockeye salmon precludes a scenario in which fish from the three creeks constitute a single population that segregates by body size. Rather, significant phenotypic differentiation suggests that strong divergent selection occurs on the phenotypic traits despite the homogenizing effects of gene flow.

Plasma vitamins E and A and risk of bladder cancer: a case–control analysis - Dong Liang; Jie Lin; H. Barton Grossman; Jing Ma; Bo Wei; Colin P. Dinney; Xifeng Wu (Cancer Causes & Control, 2008)

Cloning and infection response of tumour‐necrosis factor alpha in large yellow croaker Pseudosciaena crocea (Richardson) - F. J. Xie; Z. P. Zhang; P Lin; S. H Wang; Z. H Zou; Y. L. Wang (Journal of Fish Biology, 2008)
In this article, reverse transcriptase polymerase chain reaction (RT‐PCR) and real‐time PCR were used to clone the tumour‐necrosis factor alpha (TNF‐α) gene of the large yellow croaker Pseudosciaena crocea (Richardson) and to analyse its response to bacterial infection. The full‐length cDNA of TNF‐α contained a 5′‐untranslated region (5′‐UTR) of 68 bp, followed by an open reading frame (ORF) of 759 bp and a 3′‐UTR of 512 bp. The ORF was capable of encoding 252 amino acids with an estimated molecular mass of 28 kDa. In the 3′‐UTR, there were two putative endotoxin‐responsive motifs and five mRNA instability motifs. The deduced peptide had a transmembrane domain and a TNF‐α family signature. Multiple sequence alignments indicated that P. crocea TNF‐α shares relatively high similarity with both teleost and mammalian TNF‐α. Phylogenetic analysis showed that teleost TNF‐α was located independently in a different branch compared with mammalian TNF‐α. Real‐time PCR analysis demonstrated that the expression of TNF‐α in the head kidney of the P. crocea injected with Vibrio parahaemolyticus was most significantly higher than that of the control group at 2 and 4 days. In blood, at 2 days post‐injection, TNF‐α expression was significantly higher than that of the control group, while at 4 days post‐injection, it was most significantly higher than that of the control group.

Characterization of novel microsatellite loci in the great leaf-nosed bat, Hipposideros armiger and cross-amplification in other related species - T. T. Guo; P. Y. Hua; L. K. Lin; S. Y. Zhang (Conservation Genetics, 2008)

Residential proximity to large airports and potential health impacts in New York State - S. Lin; J. P. Munsie; M. Herdt-Losavio; S. A. Hwang; K. Civerolo; K. McGarry; T. Gentile (International Archives of Occupational and Environmental Health, 2008)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

Treatment of polluted river water by a gravel contact oxidation system constructed under riverbed - D. F. Juang; W. P. Tsai; W. K. Liu; J. H. Lin (International Journal of Environmental Science and Technology, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Effect of low-intensity laser radiation of the red spectrum on some properties of erythrocytes in Wistar rats - N. S. Lin’kova; O. P. Gorshkova; V. N. Shuvaeva; D. P. Dvoretskii (Bulletin of Experimental Biology and Medicine, 2008)

Release of intracellular Zn2+ in cultured neurons after brief exposure to low concentrations of exogenous nitric oxide - Wei Lin; Bhavana Mohandas; Charles P. Fontaine; Robert A. Colvin (BioMetals, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

High expression of capsid protein of red‐spotted grouper nervous necrosis virus in an avian cell line requires viral RNA2 non‐coding regions - J N Huang; L Lin; S P Weng; J G He (Journal of Fish Diseases, 2007)

Optical Imaging of the Adoptive Transfer of Human Endothelial Cells in Mice Using Anti-Human CD31 Monoclonal Antibody - Alexei A. Bogdanov; Charles P. Lin; Hye-Won Kang (Pharmaceutical Research, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

A multicopper oxidase is essential for manganese oxidation and laccase‐like activity in Pedomicrobium sp. ACM 3067 - Justin P. Ridge; Marianne Lin; Eloise I. Larsen; Mark Fegan; Alastair G. McEwan; Lindsay I. Sly (Environmental Microbiology, 2007)
Summary Pedomicrobium sp. ACM 3067 is a budding‐hyphal bacterium belonging to the α‐ Proteobacteria which is able to oxidize soluble Mn 2+ to insoluble manganese oxide. A cosmid, from a whole‐genome library, containing the putative genes responsible for manganese oxidation was identified and a primer‐walking approach yielded 4350 bp of novel sequence. Analysis of this sequence showed the presence of a predicted three‐gene operon, mox CBA. The mox A gene product showed homology to multicopper oxidases (MCOs) and contained the characteristic four copper‐binding motifs (A, B, C and D) common to MCOs. An insertion mutation of mox A showed that this gene was essential for both manganese oxidation and laccase‐like activity. The mox B gene product showed homology to a family of outer membrane proteins which are essential for Type I secretion in Gram‐negative bacteria. mox BA has not been observed in other manganese‐oxidizing bacteria but homologues were identified in the genomes of several bacteria including Sinorhizobium meliloti 1021 and Agrobacterium tumefaciens C58. These results suggest that mox BA and its homologues constitute a family of genes encoding an MCO and a predicted component of the Type I secretion system.

Analysis of extended HLA haplotypes in multiple sclerosis and narcolepsy families confirms a predisposing effect for the class I region in Tasmanian MS patients - Justin P. Rubio; Melanie Bahlo; Jim Stankovich; Rachel K. Burfoot; Laura J. Johnson; Stewart Huxtable; Helmut Butzkueven; Ling Lin; Bruce V. Taylor; Terence P. Speed; Trevor J. Kilpatrick; Emmanuel Mignot; et al. (Immunogenetics, 2007)

Overexpression of proline oxidase induces proline-dependent and mitochondria-mediated apoptosis - Chien-an A. Hu; Steven P. Donald; Jian Yu; Wei-Wen Lin; Zhihe Liu; Gary Steel; Cassandra Obie; David Valle; James M. Phang (Molecular and Cellular Biochemistry, 2007)

Introgression mapping in the grasses - Julie King; Ian P. Armstead; Iain S. Donnison; John A. Harper; Luned A. Roberts; Howard Thomas; Helen Ougham; Ann Thomas; Lin Huang; Ian P. King (Chromosome Research, 2007)

Characterizing the severe turbulence environments associated with commercial aviation accidents. A real-time turbulence model (RTTM) designed for the operational prediction of hazardous aviation turbulence environments - M. L. Kaplan; J. J. Charney; K. T. Waight; K. M. Lux; J. D. Cetola; A. W. Huffman; A. J. Riordan; S. D. Slusser; M. T. Kiefer; P. S. Suffern; Y.-L. Lin (Meteorology and Atmospheric Physics, 2006)

High pressure elasticity and phase transformation in brucite, Mg(OH)2 - K. P. Jayachandran; Lin-gun Liu (Physics and Chemistry of Minerals, 2006)

Antizyme, a natural ornithine decarboxylase inhibitor, induces apoptosis of haematopoietic cells through mitochondrial membrane depolarization and caspases’ cascade - G.-Y. Liu; Y.-F. Liao; P.-C. Hsu; W.-H. Chang; M.-C. Hsieh; C.-Y. Lin; T.-C. Hour; M.-C. Kao; G. J. Tsay; H.-C. Hung (Apoptosis, 2006)

Modeling dynamics of stable carbon isotopic exchange between a boreal forest ecosystem and the atmosphere - BAOZHANG CHEN; JING M. CHEN; LIN HUANG; PIETER P. TANS (Global Change Biology, 2006)
Stable isotopes of CO 2 contain unique information on the biological and physical processes that exchange CO 2 between terrestrial ecosystems and the atmosphere. In this study, we developed an integrated modeling system to simulate dynamics of stable carbon isotope of CO 2 , as well as moisture, energy, and momentum, between a boreal forest ecosystem and the atmosphere, as well as their transport/mixing processes through the convective boundary layer (CBL), using remotely sensed surface parameters to characterize the surface heterogeneity. It has the following characteristics: (i) it accounts for the influences of the CBL turbulent mixing and entrainment of the air aloft; (ii) it scales individual leaf‐level photosynthetic discrimination up to the whole canopy (Δ canopy ) through the separation of sunlit and shaded leaf groups; (iii) it has the capacity to examine the detailed interrelationships among plant water‐use efficiency, isotope discrimination, and vapor pressure deficit; and (iv) it has the potential to investigate how an ecosystem discriminates against 13 C at various time and spatial scales. The monthly mean isotopic signatures of ecosystem respiration (i.e. δ 13 C R ) used for isotope flux calculation are retrieved from the nighttime flask data from the intensive campaigns (1998–2000) at 20 m level on Fraserdale tower, and the data from the growing season in 1999 are used for model validation. Both the simulated CO 2 mixing ratio and δ 13 C of CO 2 at the 20 m level agreed with the measurements well in different phases of the growing season. On a diurnal basis, the greatest photosynthetic discrimination at canopy level (i.e. Δ canopy ) occurred early morning and late afternoon with a varying range of 10–26‰. The diurnal variability of Δ canopy was also associated with the phases of growing season and meteorological variables. The annual mean Δ canopy in 1999 was computed to be 19.58‰. The monthly averages of Δ canopy varied between 18.55‰ and 20.84‰ with a seasonal peak during the middle growing season. Because of the strong opposing influences of respired and photosynthetic fluxes on forest air (both CO 2 and 13 CO 2 ) on both the diurnal and seasonal time scales, CO 2 was consistently enriched with the heavier 13 C isotope (less negative δ 13 C) from July to October and depleted during the remaining months, whereas on a diurnal basis, CO 2 was enriched with the heavier 13 C in the late afternoon and depleted in early morning. For the year 1999, the model results reveal that the boreal ecosystem in the vicinity of Fraserdale tower was a small sink with net uptake of 29.07 g 12 C m −2 yr −1 and 0.34 g 13 C m −2 yr −1 .

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

Identification of neurons that express 5-hydroxytryptamine4 receptors in intestine - Daniel P. Poole; Bo Xu; Shir Lin Koh; Billie Hunne; Ian M. Coupar; Helen R. Irving; Katsuhiro Shinjo; John B. Furness (Cell and Tissue Research, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Albino inflorescence proliferation of Dendrocalamus latiflorus - C. S. Lin; M. C. Tseng; P. I. Hong; W. C. Chang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Enhanced viability of a nervous necrosis virus‐infected stable cell line over‐expressing a fusion product of the zfBcl‐x L and green fluorescent protein genes - S‐P Chen; H‐L Yang; H‐Y Lin; M‐C Chen; J‐L Wu; J‐R Hong (Journal of Fish Diseases, 2006)
Nervous necrosis virus (NNV) infection induces host cell apoptosis by an ill‐understood process. We utilized a fusion between enhanced green fluorescent protein (EGFP) and the zfBcl‐x L gene in GL‐av cells to select for zfBcl‐x L stable cell lines and to assess the effectiveness of the anti‐apoptotic protein Bcl‐x L in circumventing NNV‐induced cell death. Stable EGFP and EGFP‐Bcl‐x L ‐expressing clones were obtained at high purity within 2.5–3 months. In the latter, the EGFP‐Bcl‐x L fusion protein (approximately 58.2 kDa, as ascertained by Western blot) was predominantly targeted to mitochondria. We assayed for apoptosis in red‐spotted grouper NNV Tainan no. 1 (RGNNV TN1)‐infected cells with terminal deoxynucleotidyl transferase (TdT)‐mediated end labelling (TUNEL) of DNA at different virus doses. NNV infection of NNV Bcl‐x L GL‐av cell line revealed a protective effect, with a decrease in TUNEL‐positive cells of 7%, 8% and 31.8% at 24, 48 and 72 h, respectively. In addition, RGNNV infection of the Bcl‐x L GL‐av cell line revealed a protective effect, with an enhanced viability of 3%, 40% and 73% at 24, 48, and 72 h, respectively. We conclude that NNV‐induced apoptotic cell death can be lessened in transgenic grouper fish cells.

Detection and characterisation of a second potyvirus from Thunberg fritillary in China - J. Chen; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; C.-B. Wei; L. Lin; J.-P. Chen (Archives of Virology, 2006)

Use of a fluorescent membrane probe to identify zooxanthellae in hospite among dissociated endoderm cell culture from coral - C.-S. Chen; H.-P. Lin; C.-C. Yeh; L.-S. Fang (Protoplasma, 2005)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

Characterisation of the welsh onion isolate of Shallot yellow stripe virus from China - J. Chen; C.-B. Wei; H.-Y. Zheng; Y.-H. Shi; M. J. Adams; L. Lin; Q.-Y. Zhang; S.-J. Wang; J.-P. Chen (Archives of Virology, 2005)

Acute Toxicity of Thallium to Daphnia magna and Ceriodaphnia dubia - T.-S. Lin; P. Meier; J. Nriagu (Bulletin of Environmental Contamination and Toxicology, 2005)

Components of Honeybee Royal Jelly as Deterrents of the Parasitic Varroa Mite, Varroa destructor - F. P. Drijfhout; J. Kochansky; S. Lin; N. W. Calderone (Journal of Chemical Ecology, 2005)

A new potyvirus from Thunberg fritillary (Fritillaria thunbergii Miq.) in Zhejiang, China - C.-B. Wei; J. Chen; Q.-Y. Zhang; Y.-H. Shi; L. Lin; H.-Y. Zheng; M. J. Adams; J.-P. Chen (Archives of Virology, 2005)

The nonlinear elasticity and related properties of anhydrous and hydrous γ-Mg2SiO4: a theoretical study - K. P. Jayachandran; Lin-gun Liu (Physics and Chemistry of Minerals, 2005)

Perfluorinated Compounds in Aquatic Organisms at Various Trophic Levels in a Great Lakes Food Chain - Kurunthachalam Kannan; Lin Tao; Ewan Sinclair; Stephanie D Pastva; Dave J Jude; John P Giesy (Archives of Environmental Contamination and Toxicology, 2005)

Neutrophil Migration in Opposing Chemoattractant Gradients Using Microfluidic Chemotaxis Devices - Francis Lin; Connie Minh-Canh Nguyen; Shur-Jen Wang; Wajeeh Saadi; Steven P. Gross; Noo Li Jeon (Annals of Biomedical Engineering, 2005)

Formation and Emission of Chlorinated by-Products from a Bench-Scale Packed-Bed Odor Scrubber - Chi-Wen Lin; Daniel P. Y. Chang (Water, Air, & Soil Pollution, 2005)

Evaluation of Genotoxicity of Combined Pollution by Cadmium and Atrazine - A. J. Lin; Y. G. Zhu; Y. P. Tong; C. N. Geng (Bulletin of Environmental Contamination and Toxicology, 2005)

Peptide mimotopes of phomopsins: Identification, characterization and application in an immunoassay - Meng Yu; Khin Than; Steve Colegate; Brian Shiell; Wojtek P. Michalski; Stephen Prowse; Lin-Fa Wang (Molecular Diversity, 2005)

Further molecular characterisation of potyviruses infecting aroid plants for medicinal use in China - Y.-H. Shi; X.-Y. Hong; J. Chen; M. J. Adams; H.-Y. Zheng; L. Lin; B.-X. Qin; J.-P. Chen (Archives of Virology, 2005)

The role of halogen substitution in classical cannabinoids: A CB1 pharmacophore model - Spyros P. Nikas; Jolanta Grzybowska; Demetris P. Papahatjis; Avgui Charalambous; Ali R. Banijamali; Ravi Chari; Pusheng Fan; Therapia Kourouli; Sonyuan Lin; Albert J. Nitowski; Gilbert Marciniak; Yan Guo; et al. (The AAPS Journal, 2004)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Differential Response of Four Cyanobacterial and Green Algal Species to Triazophos, Fentin Acetate, and Ethephon - J. Ma; F. Lin; W. Qin; P. Wang (Bulletin of Environmental Contamination and Toxicology, 2004)

Role and differential expression of calpastatin mRNA and protein in cultured cardiomyocytes exposed to hypoxic stress - Huey Lin; Milish P. Risbood; Atul Jain; Victor Vacanti; Techung Lee (Molecular and Cellular Biochemistry, 2004)

A new potyvirus from tuberose ( Polianthes tuberosa ) in China - L. Lin; H.-Y. Zheng; J. Chen; J.-P. Chen; Q.-Y. Zhang; M.-F. Zhao; J. F. Antoniw; M. J. Adams (Archives of Virology, 2004)

Biological functions of the cytoplasmic TGBp1 inclusions of bamboo mosaic potexvirus - H.-T. Hsu; Y.-H. Hsu; I.-P. Bi; N.-S. Lin; B.-Y. Chang (Archives of Virology, 2004)

Kinetic Studies on the Effects of Organophosphorus Pesticides on the Growth of Microcystis aeruginosa and Uptake of the Phosphorus Forms - P.-J. Zhou; H. Shen; J. Lin; L.-R. Song; Y.-D. Liu; Z.-B. Wu (Bulletin of Environmental Contamination and Toxicology, 2004)

Kinetic Studies on the Combined Effects of Lanthanum and Cerium on the Growth of Microcystis aeruginosa and their Accumulation by M. aeruginosa - P.-J. Zhou; J. Lin; H. Shen; T. Li; L.-R. Song; Y.-W. Shen; Y.-D. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Detection and classification of allexiviruses from garlic in China - J. Chen; H.-Y. Zheng; J. F. Antoniw; M. J. Adams; J.-P. Chen; L. Lin (Archives of Virology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

A virus related to Soybean mosaic virus from Pinellia ternata in China and its comparison with local soybean SMV isolates - J. Chen; H.-Y. Zheng; L. Lin; M. J. Adams; J. F. Antoniw; M.-F. Zhao; Y.-F. Shang; J.-P. Chen (Archives of Virology, 2004)

QTLs for Na+ and K+ uptake of the shoots and roots controlling rice salt tolerance - H. X. Lin; M. Z. Zhu; M. Yano; J. P. Gao; Z. W. Liang; W. A. Su; X. H. Hu; Z. H. Ren; D. Y. Chao (Theoretical and Applied Genetics, 2004)

Efficacy and Safety of Cefotaxime in Combination with Metronidazole for Empirical Treatment of Brain Abscess in Clinical Practice: A Retrospective Study of 66 Consecutive Cases - A.-K. Jansson; P. Enblad; J. Sjlin (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Development of a Fragment Constant Method for Estimating the Mixture Toxicity - Z. Lin; L. Wang; P. Shi; D. Zhao; K. Yin (Archives of Environmental Contamination and Toxicology, 2004)

Occurrence and sequences of Lily mottle virus and Lily symptomless virus in plants grown from imported bulbs in Zhejiang province, China - H.-Y. Zheng; J. Chen; M.-F. Zhao; L. Lin; J.-P. Chen; J. F. Antoniw; M. J. Adams (Archives of Virology, 2003)

Annual Variations of Gonadotropin Content and Ovarian Development of Feral Female Catfish, Silurus asotus, in Central China - Hai Sh Wen; Hao R. Lin; Yu Z. Mao; Liang Wang; Ya P. Zhang (Environmental Biology of Fishes, 2003)

Historical biogeography and phylogenetic relationships of the genus Chamaecyparis (Cupressaceae) inferred from chloroplast DNA polymorphism - W. P. Wang; C. Y. Hwang; T. P. Lin; S. Y. Hwang (Plant Systematics and Evolution, 2003)

Small-angle X-ray scattering measurement of the internal microstructure of natural zircon crystals - A. P. Radlinski; J. Claou-Long; A. L. Hinde; E. Z. Radlinska; J.-S. Lin (Physics and Chemistry of Minerals, 2003)

Evidence for the existence of some dissociation in an otherwise strong linkage disequilibrium between mitochondrial and chloroplastic genomes in Cyclobalanopsis glauca - T.‐P. Lin; W.‐J. Chuang; S. S. F. Huang; S.‐Y. Hwang (Molecular Ecology, 2003)
Variations in mitochondrial DNA in Cyclobalanopsis glauca (Thunb. ex Murray) Oerst. were studied in 140 trees from 32 populations collected from within the tree's natural range. By sequencing two mitochondrial DNA intron fragments ( nad 4/3 ‐nad 4/4r and nad 7/2 ‐nad 7/3r), we revealed a total of 1788 bp and five polymorphic sites which allowed us to distinguish six mitotypes. The mitochondrial DNA markers provided replicated data to support population phylogeographical scenarios suggested previously using chloroplastic DNA markers. The gene genealogical tree of mitochondrial DNA was partially congruent with the chloroplastic DNA tree owing to the slower mutation rate and different mutational direction. Significant linkage disequilibrium existed between the two organellar genomes. Further paring analyses between fragments synthesized using different primers, accompanied by exclusion of polymorphic sites, showed that the random association could be attributed specifically to one of the polymorphic sites of the pet G‐ trn P fragment of the chloroplastic genome, and the three polymorphic sites of the nad 4/3‐ nad 4/4r fragment of the mitochondrial genome. The former was inferred to derive from paternal leakage, and the latter from recurrent mutation. These polymorphic sites were also responsible for uncoupling of the combined gene tree of mitotype and chlorotype. In conclusion, specific fragments found in this study contribute to the incomplete congruence of the two organellar lineages that otherwise associate well phylogeographically.

Nonrandom Intragenic Variations in Patterns of Codon Bias Implicate a Sequential Interplay Between Transitional Genetic Drift and Functional Amino Acid Selection - K. Lin; S. B. Tan; P. R. Kolatkar; R. J. Epstein (Journal of Molecular Evolution, 2003)

Gene content and organization of an 85-kb DNA segment from the genome of the phytopathogenic mollicute Spiroplasma kunkelii - Y. Zhao; R. W. Hammond; R. Jomantiene; E. L. Dally; I.-M. Lee; H. Jia; H. Wu; S. Lin; P. Zhang; S. Kenton; F. Z. Najar; A. Hua; et al. (Molecular Genetics and Genomics, 2003)

The extent and distribution of linkage disequilibrium in a multi-hierarchic outbred canine pedigree - Xiang-Yang Lou; Rory J. Todhunter; Min Lin; Qing Lu; Tian Liu; Zuoheng Wang; Stuart P. Bliss; George Casella; Gregory M. Acland; George Lust; Rongling Wu (Mammalian Genome, 2003)

General Toxicity Prediction Approach for Mixtures Containing Polar Narcotic Chemicals - Z. Lin; C. Wu; P. Shi; L. Wang; S. Gao (Bulletin of Environmental Contamination and Toxicology, 2003)

Tropical Glacier and Ice Core Evidence of Climate Change on Annual to Millennial Time Scales - Lonnie G. Thompson; Ellen Mosley-Thompson; M. E. Davis; P.-N. Lin; K. Henderson; T. A. Mashiotta (Climatic Change, 2003)

Photodegradation of Diesel Oil in Aqueous Solutions - P. Zhong; L. R. Kong; Z. F. Lin; G. M. Liu (Bulletin of Environmental Contamination and Toxicology, 2003)

Genetic relationships among cold, salt and drought tolerance during seed germination in an interspecific cross of tomato - M.R. Foolad; P. Subbiah; C. Kramer; G. Hargrave; G.Y. Lin (Euphytica, 2003)

Human infection by a swine influenza A (H1N1) virus in Switzerland - V. Gregory; M. Bennett; Y. Thomas; L. Kaiser; W. Wunderli; H. Matter; A. Hay; Y. P. Lin (Archives of Virology, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

A framework for integrating the songbird brain - Jarvis E.; Smith V.; Wada K.; Rivas M.; McElroy M.; Smulders T.; Carninci P.; Hayashizaki Y.; Dietrich F.; Wu X.; McConnell P.; Yu J.; et al. (Journal of Comparative Physiology A, 2002)

The Use of in Vitro Metabolic Stability for Rapid Selection of Compounds in Early Discovery Based on Their Expected Hepatic Extraction Ratios - Yau Yi Lau; Gopal Krishna; Nathan P. Yumibe; Diane E. Grotz; Elpida Sapidou; Laura Norton; Inhou Chu; Cliff Chen; A. D. Soares; Chin-Chung Lin (Pharmaceutical Research, 2002)

Specific detection ofPythium aphanidermatum from hydroponic nutrient solution by booster PCR with DNA primers developed from mitochondrial DNA - P. H. Wang; L. M. Boo; Y. S. Lin; Y. Yeh (Phytoparasitica, 2002)

Pharmacokinetic comparison of beclomethasone dipropionate extrafine aerosol from two inhaler devices in children with asthma - Lester I. Harrison; Sarala Kurup; Lin-Zhi Chen; Bruce P. Ekholm; Timothy G. Wighton; Gail G. Shapiro (European Journal of Clinical Pharmacology, 2002)

Phospholipase C interacts with Sgd1p and is required for expression of GPD1 and osmoresistance in Saccharomyces cerevisiae - H. Lin; P. Nguyen; A. Vancura (Molecular Genetics and Genomics, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

Modulation of calcium balance in tilapia larvae ( Oreochromis mossambicus ) acclimated to low-calcium environments - Chou M.-Y.; Lu F.-I.; Lin H.-C.; Hwang P.-P.; Yang C.-H. (Journal of Comparative Physiology B, 2002)

Evolutionary and taxonomic implications of conserved structural motifs between picornaviruses and insect picorna-like viruses - L. Liljas; J. Tate; T. Lin; P. Christian; J. E. Johnson (Archives of Virology, 2002)

The role of thiol compounds in increasing Agrobacterium-mediated transformation of soybean cotyledonary-node cells - P. Olhoft; K. Lin; J. Galbraith; N. Nielsen; D. Somers (Plant Cell Reports, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Exploring suitability for tropical crop cultivation in Hainan Island by SOTAL methodology - Zhang Xue-lei; S. Mantel; Zhang Gan-lin; V. W. P. van Engelen (Journal of Geographical Sciences, 2001)

Distribution of glucose-6-phosphate dehydrogenase mutations in Southeast Asia - Kuni Iwai; Akira Hirono; Hiroyuki Matsuoka; Fumihiko Kawamoto; Toru Horie; Khin Lin; Indah S. Tantular; Yoes P. Dachlan; Harsono Notopuro; Noor I. Hidayah; Abdul M. Salim; Hisaichi Fujii; et al. (Human Genetics, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Statistical optimization of gastric floating system for oral controlled delivery of calcium - Shoufeng Li; Senshang Lin; Yie W. Chien; Bruce P. Daggy; Haresh L. Mirchandani (AAPS PharmSciTech, 2001)

Allozyme variations in Michelia formosana (Kanehira) Masamune(Magnoliaceae), and the inference of a glacial refugium in Taiwan - T.-P. Lin (Theoretical and Applied Genetics, 2001)

Raman spectroscopic study of hydroxyl-clinohumite at various pressures and temperatures - C.-C. Lin; L.-G. Liu; T. P. Mernagh; T. Irifune (Physics and Chemistry of Minerals, 2000)

Mineralization of organic sulfur and its importance as a reservoir of plant-available sulfur in upland soils of north China - W. Zhou; S. T. Li; H. Wang; P. He; B. Lin (Biology and Fertility of Soils, 1999)

Flavonoids as inducers of extracellular proteins and exopolysaccharides of Sinorhizobium fredii - C. C. Lin; Y. C. Chen; S. C. Song; L. P. Lin (Biology and Fertility of Soils, 1999)

Cyclosporine Transfer from Low- and High-Density Lipoproteins Is Partially Influenced by Lipid Transfer Protein I Triglyceride Transfer Activity - Kishor M. Wasan; Ramaswamy Subramanian; Jenny Wen-Lin Chou; Manisha Ramaswamy; P. Haydn Pritchard (Pharmaceutical Research, 1999)

Cadmium-Inducible Metallothionein in Tilapia ( Oreochromis mossambicus ) - S. M. Wu *, C. F. Weng; M. J. Yu; C. C. Lin; S. T. Chen; J. C. Hwang; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1999)

Molecular Identification of a Murine Ubiquitin/60S Ribosomal Fusion Protein and Expression Study in Mouse Kidney - Lin Sun; Rudolf P. Wuthrich (Biochemical Genetics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Mitochondrion‐rich cells in the embryonic yolk sac of Oreochromis mossambicus - H. C. Lin; P. P. Hwang; T. H. Lee (Journal of Fish Biology, 1999)
By removing a small amount of yolk, tilapia embryos were dechorionated successfully as early as 30 h after fertilization. Using DASPEI, a mitochondrion‐specific fluorescent stain, we were able to determine the first appearance of the mitochondrion rich cells on the surface of the yolk sac 26 h after fertilization ( c. 2 h after the beginning of gastrula stage). However, with scanning electron microscopy examination, no apical crypt could be found until 48 h after fertilization.

Acute and Chronic Effects of Antimony Chloride (SbCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute and Chronic Effects of Indium Chloride (InCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Acute and Chronic Effects of Gallium Chloride (GaCl 3 ) on Tilapia ( Oreochromis mossambicus ) Larvae - H. C. Lin; P. P. Hwang (Bulletin of Environmental Contamination and Toxicology, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1998)

Transgenic peppermint ( Mentha × piperita L.) plants obtained by cocultivation with Agrobacterium tumefaciens - X. Niu; K. Lin; P. M. Hasegawa; R. A. Bressan; S. C. Weller (Plant Cell Reports, 1998)

Estimation of myocardial glucose utilisation with PET using the left ventricular time-activity curve as a non-invasive input function - X. Li; D. Feng; K. -P. Lin; S. -C. Huang (Medical & Biological Engineering & Computing, 1998)

Seasonal variation and origin of Particulate Organic Carbon in the lower Garonne River at La Reole (southwestern France) - E. Veyssy; H. Etcheber; R.G. Lin; P. Buat-Menard; E. Maneux (Hydrobiologia, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1997)

CaEGTA uncompetitively inhibits calcium activation of whorl morphogenesis inAcetabularia - Lionel G. Harrison; G. Donaldson; W. Lau; M. Lee; B. P. Lin; S. Lohachitranont; I. Setyawati; J. Yue (Protoplasma, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Raman spectra of high-pressure polymorphs of SiO 2 at various temperatures - Lin-gun Liu; T. P. Mernagh; W. O. Hibberson (Physics and Chemistry of Minerals, 1997)

Bcl-2 blocks peroxynitrite-induced apoptosis in HL-60 cells, an association with reactive oxygen species - K.-T. Lin; J.-Y. Xue; P. Y.-K. Wong (Inflammation Research, 1997)

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project - T.-N. Wu; Chen-Yang Shen; Saou-Hsing Liou; Guang-Yang Yang; K.-N. Ko; Show-Lin Chao; Chao-Chun Hsu; P.-Y. Chang (International Archives of Occupational and Environmental Health, 1997)

Physical mapping of four RAPDs in the B chromosome of maize - B.-Y. Lin; H.-P. Chou (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)

Suggestive evidence for linkage of schizophrenia to markers on chromosome 13 in Caucasian but not Oriental populations - M.-W. Lin; P. Sham; Hai-Gwo Hwu; David Collier; Robin Murray; John F. Powell (Human Genetics, 1997)

Temperature dependence of Raman spectra of the quartz- and rutile-types of GeO 2 - Terrence P. Mernagh; Lin-gun Liu (Physics and Chemistry of Minerals, 1997)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

N-Nitroso-N-(3-keto-1,2-butanediol)-3′-nitrotyramine - C. -J. Wang; H. -P. Huang; T. -H. Tseng; Y. -L. Lin; S. -J. Shiow (Archives of Toxicology, 1995)

Different sensitivities to cadmium in tilapia larvae (Oreochromis mossambicus; teleostei) - P. P. Hwang; S. W. Lin; H. C. Lin (Archives of Environmental Contamination and Toxicology, 1995)

A new immunostimulatory complex (PICKCa) in experimental rabies: antiviral and adjuvant effects - H. X. Lin; C. Gontier; M-F. Saron; P. Perrin (Archives of Virology, 1993)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Morbidity and mortality in workers occupationally exposed to pesticides - Donald P. Morgan; Lawrence I. Lin; Heidi H. Saikaly (Archives of Environmental Contamination and Toxicology, 1980)

Blood organochlorine pesticide concentrations, clinical hematology and biochemistry in workers occupationally exposed to pesticides - Donald P. Morgan; Lawrence I. Lin (Archives of Environmental Contamination and Toxicology, 1978)

Urinary excretion of paranitrophenol and alkyl phosphates following ingestion of methyl or ethyl parathion by human subjects - Donald P. Morgan; Herbert L. Hetzler; Edwin F. Slach; Lawrence I. Lin (Archives of Environmental Contamination and Toxicology, 1977)